Method for manufacturing toner for electrostatic charge image development
By adding a water-soluble addition polymer to the aggregation particles in the agglomeration fusion method, the method addresses the issue of coarse grains in toner production, enhancing dispersion stability and maintaining charging properties under high temperature and humidity conditions.
Patent Information
- Application Number
- JP2024155480
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-09-12
- Filing Date
- 2024-09-10
- Publication Date
- 2025-03-25
AI Technical Summary
The agglomeration fusion method for manufacturing toner for developing electrostatic charge images often results in coarse grains due to insufficient dispersion stability of the aggregation particles during the fusion step.
A method involving the addition of a specific amount of a water-soluble addition polymer between an aromatic group-containing monomer and a hydrophilic monomer to the aggregation particles, followed by heating to fusion, which improves the dispersion stability and reduces the content of coarse grains in the toner.
The method effectively reduces the content of coarse grains in the toner, maintaining the charging property even after storage at high temperature and high humidity.
Smart Images

Figure 2025040964000001 
Figure 2025040964000002 
Figure 2025040964000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a toner for developing an electrostatic image. [Background technology]
[0002] In the field of electrophotography, with the development of electrophotographic systems, there is a demand for the development of electrophotographic toners that can handle higher image quality and higher speeds. In order to obtain a toner with a narrow particle size distribution and small particle size in response to the demand for higher image quality, toners are produced by the aggregation and coalescence method (emulsion aggregation method, aggregation and fusion method), in which fine resin particles and the like are aggregated and fused in an aqueous medium to obtain a toner.
[0003] For example, Patent Document 1 describes a method for producing a toner for developing electrostatic images, which is intended to provide a method for producing a toner for developing electrostatic images that can produce a toner having excellent heat resistance and storage stability, and includes, in this order, steps of: step 1: aggregating resin particles X in an aqueous medium to obtain aggregated particles 1; step 2: aggregating resin particles Y containing a polyester resin B having an aromatic ring concentration of 4.8 mmol / g or more to the aggregated particles 1 obtained in step 1 to obtain aggregated particles 2; and step 3: adding an amphipathic molecule having a naphthalene ring to the aggregated particles 2 obtained in step 2, followed by heating to fuse the particles to obtain fused particles. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent Publication No. 2021-182045 Summary of the Invention [Problem to be solved by the invention]
[0005] When producing toner by the aggregation fusion method, in the fusion step, the binder resin of the aggregated particles is softened to integrate each particle in the aggregated particle, but if the dispersion stability of the aggregated particles is insufficient, there is a problem that the aggregated particles will fuse together and the particles will tend to become coarse. Through the study by the present inventors, it was found that although the technology described in Patent Document 1 can obtain a toner with excellent heat-resistant storage stability by adding an amphipathic molecule having a naphthalene ring in step 3, the dispersion stability of the aggregated particles during fusion can be further improved. The present invention relates to a method for producing a toner for developing electrostatic images, which can reduce the content of coarse particles (coarse toner particles) in the toner obtained by the aggregation and fusion method. [Means for solving the problem]
[0006] The present inventors have discovered that, in a method for producing a toner for developing electrostatic images, which includes aggregation and fusion steps, the content of coarse particles in the resulting toner can be reduced by adding a specific amount of a water-soluble addition polymer of an aromatic group-containing monomer and a hydrophilic monomer to the aggregated particles in the fusion step, and then fusing the particles by raising the temperature.
[0007] That is, the present invention relates to the following [1]. [1] A method for producing a toner for developing electrostatic images, comprising the following steps 1 and 2 in this order: Step 1: aggregating resin particles in an aqueous medium to obtain aggregated particles; Step 2: A step of adding 0.2 parts by mass or more and 30 parts by mass or less of a water-soluble addition polymer of an aromatic group-containing monomer and a hydrophilic monomer to the aggregated particles obtained in step 1 relative to 100 parts by mass of the binder resin in the aggregated particles, and then heating the mixture to fuse the mixture to obtain fused particles. Effect of the Invention
[0008] According to the present invention, there is provided a method for producing a toner for developing an electrostatic image, which can reduce the content of coarse particles in the toner obtained by the aggregation and fusion method. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] [Method of manufacturing toner for developing electrostatic images] The method for producing a toner for developing electrostatic images of the present invention includes the following steps 1 and 2 in this order. Step 1: aggregating resin particles in an aqueous medium to obtain aggregated particles; Step 2: A step of adding 0.2 parts by mass or more and 30 parts by mass or less of a water-soluble addition polymer of an aromatic group-containing monomer and a hydrophilic monomer to the aggregated particles obtained in step 1 relative to 100 parts by mass of the binder resin in the aggregated particles, and then heating the mixture to fuse the mixture to obtain fused particles. Hereinafter, the method for producing the toner for developing electrostatic images of the present invention may be simply referred to as "the production method of the present invention". Also, the toner for developing electrostatic images obtained by the production method of the present invention may be simply referred to as "toner". Also, the water-soluble addition polymer of the aromatic group-containing monomer and the hydrophilic monomer may be simply referred to as "water-soluble addition polymer F".
[0010] According to the manufacturing method of the present invention, the content of coarse particles in the toner obtained can be reduced. The reason why the above effect is obtained is not clear, but is thought to be as follows. The present invention relates to a method for producing a toner, which includes a step of aggregating resin particles in an aqueous medium to obtain aggregated particles, and then heating the aggregated particles to fuse them. The method includes adding a water-soluble addition polymer of an aromatic group-containing monomer and a hydrophilic monomer to the aggregated particles obtained in step 1 in an amount of 0.2 to 30 parts by mass per 100 parts by mass of the binder resin in the aggregated particles. The water-soluble addition polymer of an aromatic group-containing monomer and a hydrophilic monomer used in step 2 of the production method of the present invention has an aromatic group (adsorption group) in a structural unit derived from the aromatic group-containing monomer, and has a hydrophilic group (dispersion group) in a structural unit derived from the hydrophilic monomer. That is, the adsorption group and the dispersion group are in separate structural units. Therefore, the adsorption group has high mobility and is adsorbed to the aggregated particles at multiple points, and the dispersion group also has high mobility and can effectively disperse, so that the aggregation between the aggregated particles is suppressed while the fusion of the aggregated particles proceeds, and it is considered that the generation of coarse fused particles is suppressed, and the content of coarse particles in the obtained toner can be reduced. Furthermore, the toner obtained by the manufacturing method of the present invention retains its electrostatic charge even after storage at high temperature and high humidity. It is presumed that, because the molecules do not penetrate into the resin when the multi-point adsorption is performed via aromatic rings, the water-soluble copolymer is easily removed from the toner particle surface when the toner particles are washed and collected after fusion, and the residue on the toner particle surface is suppressed. Therefore, the electrostatic charge of the obtained toner is effectively exerted without being reduced, and the electrostatic charge is retained even after storage at high temperature and high humidity. It should be noted that the above-mentioned mechanism regarding the effect of the present invention is merely a presumption, and the present invention is not limited thereto.
[0011] The definitions of various terms used in this specification are given below. Regarding the "water solubility" of a polymer, when a polymer that has been dried at 105°C for 2 hours and has reached a constant weight is dissolved in 100 g of water at 25°C until it reaches saturation, the polymer is deemed to be water soluble if the amount of dissolution exceeds 10 g. When a water-insoluble polymer is an anionic polymer, the amount of dissolution is the amount of dissolution when the anionic groups of the polymer are 100% neutralized with sodium hydroxide. The "hydrophilicity" of a monomer means that when the monomer is dissolved in 100 g of ion-exchanged water at 25° C. until saturation, the amount of the monomer dissolved is 10 g or more. The amount of the monomer dissolved of the hydrophilic monomer is preferably 50 g or more. In the case of a monomer having an ionic functional group, the "hydrophilicity" means that the amount of the monomer dissolved in a state where the ionic functional group is neutralized is within the above range. With respect to hydrocarbon groups, the references "(iso or tertiary)" and "(iso)" in parentheses refer to both the cases with and without the prefixes present; the absence of the prefixes indicates normal. The term "(meth)acrylic acid" refers to at least one selected from acrylic acid and methacrylic acid, and the term "(meth)acrylate" refers to at least one selected from acrylate and methacrylate. By "styrenic compound" is meant unsubstituted or substituted styrene. Whether a resin is crystalline or amorphous is determined by the crystallinity index. The crystallinity index is defined as the ratio of the softening point of the resin to the maximum endothermic peak temperature (softening point (°C) / maximum endothermic peak temperature (°C)) in the measurement method described in the examples below. A crystalline resin is one whose crystallinity index is 0.6 or more and 1.4 or less. A non-crystalline resin is one whose crystallinity index is less than 0.6 or more than 1.4. The crystallinity index can be appropriately adjusted by the types and ratios of raw material monomers, as well as production conditions such as reaction temperature, reaction time, and cooling rate. The carboxylic acid component of the polyester resin includes not only the compound itself, but also anhydrides that decompose during the reaction to generate an acid, and alkyl esters of each carboxylic acid (alkyl groups having 1 to 3 carbon atoms). Volume Median Particle Size (D 50 )" is the particle size at which the cumulative volume frequency calculated by volume fraction is 50% starting from the smallest particle size. The coefficient of variation of particle size distribution (hereinafter, simply referred to as "CV value") is a value expressed by the following formula: In the following formula, the volume average particle size is the particle size obtained by multiplying the particle size measured on a volume basis by the proportion of particles having that particle size value, and dividing the resulting value by the number of particles. CV value (%) = [Standard deviation of particle size distribution (μm) / Volume average particle size (μm)] x 100
[0012] <Process 1> In step 1, resin particles are aggregated in an aqueous medium to obtain aggregated particles. The aggregated particles obtained in step 1 include aggregated particles 1 obtained by aggregating resin particles in an aqueous medium, and aggregated particles 2 obtained by attaching shell resin particles containing an amorphous resin to the aggregated particles 1 as cores in an aqueous medium and aggregating the cores. In this specification, the term "aggregated particles" simply refers to aggregated particles 1 or 2. In step 1, it is preferable to obtain aggregated particles 1 by aggregating colorant particles and release agent particles in addition to the resin particles, and it is more preferable to mix a resin particle dispersion, a colorant particle dispersion, and a release agent particle dispersion, and aggregate these particles to obtain aggregated particles 1. [Resin particles] The resin particle dispersion used in step 1 contains resin particles. The resin particles preferably contain an amorphous resin A. From the viewpoint of low-temperature fixability of the toner obtained, the resin particles may contain, in addition to the amorphous resin A, a crystalline polyester resin C in the same or different resin particles.
[0013] <Amorphous resin A> In the present invention, the binder resin preferably contains an amorphous resin A. Hereinafter, the amorphous resin A may be simply referred to as "resin A". Resin A is, for example, an amorphous polyester resin containing a polycondensate of an alcohol component and a carboxylic acid component, and a styrene-acrylic resin. Examples of the amorphous polyester resin include polyester resin and modified polyester resin. Examples of the modified polyester resin include urethane modified polyester resin, epoxy modified polyester resin, and composite resin containing polyester resin segment and addition polymerization resin segment. Among these, from the viewpoint of reducing the content of coarse particles in the obtained toner, resin A is preferably polyester resin, composite resin and styrene-acrylic resin, more preferably polyester resin and composite resin, and even more preferably polyester resin.
[0014] (Amorphous polyester resin) Examples of the alcohol component of the amorphous polyester resin include aliphatic diols, alkylene oxide adducts of aromatic diols, alicyclic diols, and trivalent or higher polyhydric alcohols. Among these, from the viewpoint of reducing the content of coarse particles in the toner obtained, aliphatic diols and alkylene oxide adducts of aromatic diols are preferred for polyester resins, and aliphatic diols are more preferred. From the same viewpoint, alkylene oxide adducts of aromatic diols are preferred for composite resins.
[0015] Examples of aliphatic diols include ethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,2-butanediol, 1,3-butanediol, 1,4-butanediol, 2,3-butanediol, 2,2-dimethyl-1,3-propanediol (neopentyl glycol), 1,6-hexanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,12-dodecanediol, and 3-methyl-1,5-pentanediol. Of these, ethylene glycol, 1,2-propanediol, and 2,2-dimethyl-1,3-propanediol are preferred, and 2,2-dimethyl-1,3-propanediol is more preferred. When the alcohol component contains an aliphatic diol, the content of the aliphatic diol in the alcohol component is preferably 80 mol % or more, more preferably 90 mol % or more, and 100 mol % or less, preferably 100 mol %.
[0016] The alkylene oxide adduct of an aromatic diol is preferably an alkylene oxide adduct of bisphenol A, more preferably an alkylene oxide adduct of formula (I):
[0017] [ka] (In the formula, OR 1 and R 2 O is an oxyalkylene group, and R 1 and R 2 each independently represents an ethylene group or a propylene group, x and y represent the average number of moles of alkylene oxide added and are each positive numbers, and the sum of x and y is 1 or more, preferably 1.5 or more, and 16 or less, preferably 8 or less, and more preferably 4 or less.
[0018] Examples of the alkylene oxide adduct of bisphenol A represented by formula (I) include a propylene oxide adduct of bisphenol A and an ethylene oxide adduct of bisphenol A. When the alcohol component contains an alkylene oxide adduct of bisphenol A, the content of the alkylene oxide adduct of bisphenol A in the alcohol component is preferably 80 mol% or more, more preferably 90 mol% or more, and is 100 mol% or less, preferably 100 mol%.
[0019] Examples of the alicyclic diol include hydrogenated bisphenol A [2,2-bis(4-hydroxycyclohexyl)propane] and adducts of hydrogenated bisphenol A with alkylene oxides having 2 to 4 carbon atoms (average number of moles added: 2 to 12).
[0020] Examples of trihydric or higher polyhydric alcohols include glycerin, pentaerythritol, trimethylolpropane, and sorbitol. These alcohol components may be used alone or in combination of two or more.
[0021] Examples of the carboxylic acid component of the amorphous polyester resin include dicarboxylic acids and trivalent or higher polycarboxylic acids.
[0022] Examples of dicarboxylic acids include aromatic dicarboxylic acids, aliphatic dicarboxylic acids, and alicyclic dicarboxylic acids. Among these, at least one selected from aromatic dicarboxylic acids and aliphatic dicarboxylic acids is preferred.
[0023] Examples of aromatic dicarboxylic acids include phthalic acid, isophthalic acid, and terephthalic acid. Among these, isophthalic acid and terephthalic acid are preferred. The amount of the aromatic dicarboxylic acid in the carboxylic acid component is preferably 30 mol % or more, more preferably 40 mol % or more, and further preferably 50 mol % or more, and 100 mol % or less.
[0024] The aliphatic dicarboxylic acid preferably has 2 or more, more preferably 3 or more, and preferably has 30 or less, more preferably 20 or less. Examples of the aliphatic dicarboxylic acid include oxalic acid, malonic acid, maleic acid, fumaric acid, citraconic acid, itaconic acid, glutaconic acid, succinic acid, adipic acid, sebacic acid, dodecanedioic acid, azelaic acid, and succinic acid substituted with an aliphatic hydrocarbon group having 1 to 20 carbon atoms. Examples of the succinic acid substituted with an aliphatic hydrocarbon group having 1 to 20 carbon atoms include dodecylsuccinic acid, dodecenylsuccinic acid, and octenylsuccinic acid. Among these, fumaric acid, sebacic acid, adipic acid, and succinic acid substituted with an aliphatic hydrocarbon group having 1 to 20 carbon atoms are preferred, and fumaric acid and adipic acid are more preferred. When the carboxylic acid component contains an aliphatic dicarboxylic acid, the amount of the aliphatic dicarboxylic acid in the carboxylic acid component is preferably 5 mol% or more, more preferably 10 mol% or more, even more preferably 15 mol% or more, and preferably 50 mol% or less, more preferably 45 mol% or less, even more preferably 40 mol% or less.
[0025] An example of the alicyclic dicarboxylic acid is cyclohexanedicarboxylic acid.
[0026] The trivalent or higher polyvalent carboxylic acid is preferably a trivalent carboxylic acid, such as trimellitic acid. When the carboxylic acid component contains a trivalent or higher polyvalent carboxylic acid, the amount of the trivalent or higher polyvalent carboxylic acid in the carboxylic acid component is preferably 3 mol% or more, more preferably 6 mol% or more, even more preferably 9 mol% or more, and is preferably 25 mol% or less, more preferably 20 mol% or less, even more preferably 15 mol% or less. These carboxylic acid components may be used alone or in combination of two or more.
[0027] The equivalent ratio of the carboxyl groups of the carboxylic acid component to the hydroxyl groups of the alcohol component [COOH groups / OH groups] is preferably 0.7 or more, more preferably 0.8 or more, and is preferably 1.3 or less, more preferably 1.2 or less.
[0028] When the resin A is a composite resin, an example of the addition polymerized resin segment is an addition polymer of raw material monomers containing a styrene-based compound. The styrene-based compound is an unsubstituted or substituted styrene. Examples of the substituent on the styrene include an alkyl group having 1 to 5 carbon atoms, a halogen atom, an alkoxy group having 1 to 5 carbon atoms, a sulfonic acid group, or a salt thereof. Examples of styrene-based compounds include styrene, methylstyrene, α-methylstyrene, β-methylstyrene, tert-butylstyrene, chlorostyrene, chloromethylstyrene, methoxystyrene, styrenesulfonic acid, and salts thereof. Among these, styrene is preferred. The content of the styrene-based compound in the raw material monomers of the addition polymerization resin segment is preferably 50% by mass or more, more preferably 65% by mass or more, even more preferably 75% by mass or more, and is 100% by mass or less, preferably 95% by mass or less, more preferably 90% by mass or less, even more preferably 85% by mass or less.
[0029] Examples of raw material monomers other than styrene-based compounds include (meth)acrylic acid esters such as alkyl (meth)acrylate, benzyl (meth)acrylate, and dimethylaminoethyl (meth)acrylate; olefins such as ethylene, propylene, and butadiene; halovinyls such as vinyl chloride; vinyl esters such as vinyl acetate and vinyl propionate; vinyl ethers such as methyl vinyl ether; vinylidene halides such as vinylidene chloride; and N-vinyl compounds such as N-vinylpyrrolidone. Among these, (meth)acrylic acid esters are preferred, and alkyl (meth)acrylates are more preferred. The number of carbon atoms in the alkyl group in the alkyl (meth)acrylate is preferably 1 or more, more preferably 4 or more, even more preferably 6 or more, and is preferably 24 or less, more preferably 22 or less, even more preferably 20 or less. Examples of the alkyl (meth)acrylate include methyl (meth)acrylate, ethyl (meth)acrylate, (iso)propyl (meth)acrylate, (iso- or tertiary)butyl (meth)acrylate, (iso)amyl (meth)acrylate, cyclohexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, (iso)octyl (meth)acrylate, (iso)decyl (meth)acrylate, (iso)dodecyl (meth)acrylate, (iso)palmityl (meth)acrylate, (iso)stearyl (meth)acrylate, and (iso)behenyl (meth)acrylate. Of these, 2-ethylhexyl (meth)acrylate or stearyl (meth)acrylate is preferred, stearyl (meth)acrylate is more preferred, and stearyl methacrylate is even more preferred.
[0030] When the addition polymerization resin segment contains a structural unit derived from a (meth)acrylic acid ester, the content of the (meth)acrylic acid ester in the raw material monomers of the addition polymerization resin segment is preferably 5 mass% or more, more preferably 10 mass% or more, even more preferably 15 mass% or more, and preferably 50 mass% or less, more preferably 35 mass% or less, even more preferably 25 mass% or less.
[0031] The total amount of the styrene-based compound and the (meth)acrylic acid ester in the raw material monomers of the addition polymerization resin segment is preferably 80 mass% or more, more preferably 90 mass% or more, even more preferably 95 mass% or more, and is 100 mass% or less, preferably 100 mass%.
[0032] The composite resin preferably has a constitutional unit derived from a bireactive monomer bonded via a covalent bond to a polyester resin segment and an addition polymerization resin segment. The term "structural unit derived from a bireactive monomer" refers to a unit formed by reaction of a functional group and an addition polymerizable group of a bireactive monomer. An example of the addition polymerizable group is a carbon-carbon unsaturated bond (ethylenically unsaturated bond). Examples of the bireactive monomer include addition polymerizable monomers having at least one functional group selected from a hydroxyl group, a carboxyl group, an epoxy group, a primary amino group, and a secondary amino group in the molecule. Among these, from the viewpoint of reactivity, addition polymerizable monomers having at least one functional group selected from a hydroxyl group and a carboxyl group are preferred, and addition polymerizable monomers having a carboxyl group are more preferred. Examples of the addition polymerizable monomer having a carboxy group include acrylic acid, methacrylic acid, fumaric acid, and maleic acid. Among these, from the viewpoint of reactivity in both the polycondensation reaction and the addition polymerization reaction, acrylic acid and methacrylic acid are preferred, and acrylic acid is more preferred. When the bireactive monomer is an addition polymerizable monomer having a carboxy group, the amount of the constitutional units derived from the bireactive monomer is preferably 1 mol part or more, more preferably 5 mol parts or more, even more preferably 8 mol parts or more, and preferably 30 mol parts or less, more preferably 25 mol parts or less, even more preferably 20 mol parts or less, relative to 100 mol parts of the alcohol component of the polyester resin segment of the composite resin.
[0033] The content of the polyester resin segment in the composite resin is preferably 40% by mass or more, more preferably 45% by mass or more, and even more preferably 55% by mass or more, and is preferably 95% by mass or less, more preferably 80% by mass or less, and even more preferably 70% by mass or less, based on the total amount of the polyester resin segment and the addition polymerization resin segment. The constitutional unit derived from the bireactive monomer is defined as a polyester resin segment.
[0034] The content of the addition polymerization resin segment in the composite resin is preferably 5 mass% or more, more preferably 20 mass% or more, even more preferably 30 mass% or more, and preferably 60 mass% or less, more preferably 55 mass% or less, even more preferably 45 mass% or less, based on the total amount of the polyester resin segment and the addition polymerization resin segment.
[0035] The amount of the constitutional units derived from the bireactive monomer in the composite resin is preferably 0.1 mass% or more, more preferably 0.5 mass% or more, even more preferably 0.8 mass% or more, and is preferably 8 mass% or less, more preferably 5 mass% or less, even more preferably 2 mass% or less, based on the total amount of the polyester resin segment and the addition polymerization resin segment.
[0036] The total amount of the polyester resin segment and the addition polymerization resin segment in the composite resin is preferably 80% by mass or more, more preferably 90% by mass or more, even more preferably 95% by mass or more, and is 100% by mass or less, preferably 100% by mass.
[0037] The above amount is calculated based on the ratio of the amounts of the polyester resin segment, the raw material monomer for the addition polymerization resin segment, the bireactive monomer, and the radical polymerization initiator, and the mass of the polyester resin segment, etc. is based on the mass excluding the mass of water generated by polycondensation. When a radical polymerization initiator is used, the mass of the radical polymerization initiator is calculated by including it in the addition polymerization resin segment.
[0038] (styrene-acrylic resin) Styrene-acrylic resin is an addition polymer of a styrene-based compound and an alkyl (meth)acrylate. As the styrene-based compound, the styrene-based compounds in the above-mentioned addition polymerization resin segment can be used, and styrene is preferable. The styrene-based compounds may be used alone or in combination of two or more.
[0039] In the raw material monomers of the styrene-acrylic resin, the content of the styrene-based compound is preferably 65 mass% or more, more preferably 70 mass% or more, even more preferably 75 mass% or more, and preferably 95 mass% or less, more preferably 90 mass% or less, even more preferably 85 mass% or less.
[0040] The number of carbon atoms in the alkyl group in the alkyl (meth)acrylate is preferably 1 or more, more preferably 3 or more, and is preferably 24 or less, more preferably 22 or less, and even more preferably 20 or less. Examples of the alkyl (meth)acrylate include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, iso or tertiary butyl (meth)acrylate, iso amyl (meth)acrylate, cyclohexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, iso octyl (meth)acrylate, iso decyl (meth)acrylate, iso dodecyl (meth)acrylate, iso palmityl (meth)acrylate, iso stearyl (meth)acrylate, iso behenyl (meth)acrylate, and the like. Preferably, iso or tertiary butyl (meth)acrylate, more preferably n-butyl acrylate. The alkyl (meth)acrylate may be used alone or in combination of two or more.
[0041] In the raw material monomers of the styrene-acrylic resin, the content of alkyl (meth)acrylate is preferably 5 mass% or more, more preferably 10 mass% or more, even more preferably 15 mass% or more, and preferably 30 mass% or less, more preferably 25 mass% or less, even more preferably 20 mass% or less.
[0042] The styrene-acrylic resin may contain a structural unit derived from a raw material monomer other than a styrene-based compound and an alkyl (meth)acrylate. Examples of the raw material monomer other than a styrene-based compound and an alkyl (meth)acrylate include (meth)acrylic acid esters such as benzyl (meth)acrylate and dimethylaminoethyl (meth)acrylate; olefins such as ethylene, propylene, and butadiene; halovinyls such as vinyl chloride; vinyl esters such as vinyl acetate and vinyl propionate; vinyl ethers such as methyl vinyl ether; vinylidene halides such as vinylidene chloride; and N-vinyl compounds such as N-vinylpyrrolidone. These raw material monomers may be used alone or in combination of two or more. The polymerization form of the styrene-acrylic resin may be either a random or block polymerization form.
[0043] <Method of manufacturing amorphous resin A> (Method of producing polyester resin) The polyester resin can be produced, for example, by polycondensing raw material monomers containing an alcohol component and a carboxylic acid component. The polycondensation of the alcohol component and the carboxylic acid component can be carried out, for example, in an inert gas atmosphere, in the presence of an esterification catalyst, an esterification promoter, a polymerization inhibitor, etc., as necessary, at a temperature of about 120°C or higher and 250°C or lower. Examples of the esterification catalyst include tin compounds such as dibutyltin oxide and tin(II) di(2-ethylhexanoate), and titanium compounds such as titanium diisopropoxybis(triethanolaminate). Examples of the esterification promoter that can be used together with the esterification catalyst include gallic acid (3,4,5-trihydroxybenzoic acid). The amount of the esterification catalyst used is preferably 0.01 parts by mass or more and 10 parts by mass or less based on 100 parts by mass in total of the alcohol component and the carboxylic acid component which are raw material monomers for the polyester resin. The amount of the esterification promoter used is preferably 0.001 part by mass or more and 1 part by mass or less based on 100 parts by mass in total of the alcohol component and the carboxylic acid component. Furthermore, examples of the polymerization inhibitor include radical polymerization inhibitors such as 4-tert-butylcatechol. When a polymerization inhibitor is used, the amount of the polymerization inhibitor used is preferably 0.001 part by mass or more and 1 part by mass or less based on 100 parts by mass of the total amount of the alcohol component and the carboxylic acid component.
[0044] (Method of manufacturing composite resin) The composite resin may be produced, for example, by a method including a step A of polycondensing an alcohol component and a carboxylic acid component, and a step B of addition polymerizing raw material monomers of the addition polymerization resin segment and a bireactive monomer. Step B may be carried out after step A, step B may be carried out after step A, or step A and step B may be carried out simultaneously. In step A, a part of the carboxylic acid component is subjected to a polycondensation reaction, and then step B is carried out, and thereafter the remainder of the carboxylic acid component is added to the polymerization system to further proceed with the polycondensation reaction of step A and the polycondensation reaction with, for example, a carboxy group possessed by the bireactive monomer or the constituent unit derived from the bireactive monomer.
[0045] In the step A, if necessary, the esterification catalyst and the esterification promoter described in the above-mentioned method for producing the polyester resin may be used in the same amounts to carry out polycondensation. When a monomer having an unsaturated bond such as fumaric acid is used in the polycondensation, the polymerization inhibitor described in the above-mentioned method for producing the polyester resin may be used in the same amount as above, if necessary. The temperature of the polycondensation reaction is preferably 120° C. or higher, more preferably 150° C. or higher, and even more preferably 180° C. or higher, and is preferably 250° C. or lower, and more preferably 240° C. or lower. The polycondensation may be carried out in an inert gas atmosphere.
[0046] Examples of the radical polymerization initiator for the addition polymerization in step B include peroxides such as dibutyl peroxide, persulfates such as sodium persulfate, and azo compounds such as 2,2'-azobis(2,4-dimethylvaleronitrile). The amount of the radical polymerization initiator used is preferably 1 part by mass or more and 20 parts by mass or less based on 100 parts by mass of the raw material monomer of the addition polymerization resin segment. The temperature of the addition polymerization is preferably 110° C. or higher, more preferably 130° C. or higher, and preferably 240° C. or lower, more preferably 230° C. or lower, and further preferably 220° C. or lower.
[0047] (Method of manufacturing styrene-acrylic resin) The styrene-acrylic resin can be produced by addition polymerization of raw material monomers in the same manner as in step B above.
[0048] <Physical properties of amorphous resin A> The softening point of Resin A is preferably 70° C. or higher, more preferably 85° C. or higher, and even more preferably 95° C. or higher, and is preferably 140° C. or lower, more preferably 130° C. or lower, and even more preferably 120° C. or lower. The glass transition temperature of resin A is preferably 35°C or higher, more preferably 40°C or higher, even more preferably 45°C or higher, and preferably 75°C or lower, more preferably 70°C or lower, even more preferably 65°C or lower.
[0049] The acid value of the polyester resin is preferably 5 mgKOH / g or more, more preferably 10 mgKOH / g or more, even more preferably 15 mgKOH / g or more, and is preferably 35 mgKOH / g or less, more preferably 30 mgKOH / g or less, even more preferably 25 mgKOH / g or less.
[0050] The softening point, glass transition temperature and acid value of Resin A can be appropriately adjusted by the type and amount of raw material monomer used, as well as production conditions such as reaction temperature, reaction time and cooling rate, and these values can be determined by the methods described in the examples. When two or more resins A are used in combination, it is preferable that the softening point, glass transition temperature and acid value of at least one of them are each within the above-mentioned ranges, and it is more preferable that the softening point, glass transition temperature and acid value of the mixture of these resins are each within the above-mentioned ranges.
[0051] From the viewpoint of low-temperature fixability, the content of resin A in the resin particles is preferably 70% by mass or more, more preferably 80% by mass or more, and even more preferably 90% by mass or more, and 100% by mass or less.
[0052] From the viewpoint of low-temperature fixability, the content of resin A in the toner particles is preferably 65% by mass or more, more preferably 70% by mass or more, even more preferably 75% by mass or more, and preferably 98% by mass or less, more preferably 95% by mass or less, even more preferably 90% by mass or less.
[0053] <Crystalline polyester resin C> The crystalline polyester resin C is, for example, a crystalline polyester resin which is a polycondensation product of an alcohol component and a carboxylic acid component. The crystalline polyester resin is a polycondensation product of an alcohol component and a carboxylic acid component. The alcohol component is preferably an α,ω-aliphatic diol. The α,ω-aliphatic diol has preferably 2 or more, more preferably 4 or more, even more preferably 6 or more, and preferably 16 or less, more preferably 14 or less, even more preferably 12 or less. Examples of α,ω-aliphatic diols include ethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 1,13-tridecanediol, and 1,14-tetradecanediol. Among these, 1,6-hexanediol, 1,10-decanediol, and 1,12-dodecanediol are preferred, and 1,10-decanediol is more preferred.
[0054] The amount of α,ω-aliphatic diol in the alcohol component is preferably 80 mol% or more, more preferably 85 mol% or more, even more preferably 90 mol% or more, even more preferably 95 mol% or more, and is 100 mol% or less, preferably 100 mol%.
[0055] The alcohol component may contain other alcohol components different from the α,ω-aliphatic diol. Examples of the other alcohol components include aliphatic diols other than α,ω-aliphatic diols, such as 1,2-propanediol and neopentyl glycol; aromatic diols, such as alkylene oxide adducts of bisphenol A; and trihydric or higher alcohols, such as glycerin, pentaerythritol, and trimethylolpropane. These alcohol components may be used alone or in combination.
[0056] The carboxylic acid component is preferably an aliphatic dicarboxylic acid, more preferably a straight-chain aliphatic dicarboxylic acid. The aliphatic dicarboxylic acid has preferably 4 or more, more preferably 8 or more, and even more preferably 10 or more carbon atoms, and preferably 14 or less, and more preferably 12 or less. Examples of aliphatic dicarboxylic acids include fumaric acid, sebacic acid, dodecanedioic acid, and tetradecanedioic acid. Among these, sebacic acid and dodecanedioic acid are preferred, and sebacic acid is more preferred. These carboxylic acid components may be used alone or in combination.
[0057] The amount of aliphatic dicarboxylic acid in the carboxylic acid component is preferably 80 mol% or more, more preferably 85 mol% or more, even more preferably 90 mol% or more, even more preferably 95 mol% or more, and is 100 mol% or less, preferably 100 mol%.
[0058] The carboxylic acid component may contain other carboxylic acid components different from the aliphatic dicarboxylic acid. Examples of other carboxylic acid components include aromatic dicarboxylic acids such as terephthalic acid and isophthalic acid, and polyvalent carboxylic acids having three or more carboxylic acids. These carboxylic acid components may be used alone or in combination.
[0059] The equivalent ratio of the carboxyl groups of the carboxylic acid component to the hydroxyl groups of the alcohol component [COOH groups / OH groups] is preferably 0.7 or more, more preferably 0.8 or more, and is preferably 1.3 or less, more preferably 1.2 or less.
[0060] The crystalline polyester resin can be produced, for example, by the same method as that for the amorphous polyester resin described above.
[0061] <Physical properties of crystalline polyester resin C> The softening point of the crystalline polyester resin C is preferably 60°C or higher, more preferably 70°C or higher, and even more preferably 80°C or higher from the viewpoint of the storage stability of the toner, and is preferably 150°C or lower, more preferably 120°C or lower, and even more preferably 100°C or lower from the viewpoint of further improving the low-temperature fixing ability. The melting point of the crystalline polyester resin C is preferably 50°C or higher, more preferably 60°C or higher, and even more preferably 70°C or higher from the viewpoint of the storage stability of the toner, and is preferably 100°C or lower, more preferably 90°C or lower, and even more preferably 80°C or lower from the viewpoint of further improving the low-temperature fixing ability.
[0062] The acid value of the crystalline polyester resin C is preferably 5 mgKOH / g or more, more preferably 10 mgKOH / g or more, and preferably 35 mgKOH / g or less, more preferably 25 mgKOH / g or less, and even more preferably 20 mgKOH / g or less. The softening point, melting point and acid value of the crystalline polyester resin C can be appropriately adjusted by the type and amount of the raw material monomer, as well as production conditions such as reaction temperature, reaction time and cooling rate, and are determined by the method described in the Examples below. When two or more types of crystalline polyester resin C are used in combination, it is preferable that the softening point, melting point and acid value obtained as a mixture thereof are each within the above-mentioned ranges.
[0063] When the resin particles contain crystalline polyester resin C, the mass ratio of amorphous resin A to crystalline polyester resin C in the resin particles [amorphous resin A / crystalline polyester resin C] is preferably 95 / 5 or less, more preferably 90 / 10 or less, even more preferably 85 / 15 or less, and is preferably 60 / 40 or more, more preferably 65 / 35 or more, even more preferably 70 / 30 or more. When the resin particles contain crystalline polyester resin C, the content of crystalline polyester resin C in the toner particles is preferably 5% by mass or more, more preferably 10% by mass or more, even more preferably 15% by mass or more, from the viewpoint of low-temperature fixability, and is preferably 40% by mass or less, more preferably 35% by mass or less, even more preferably 30% by mass or less.
[0064] [Method for producing resin particle dispersion] The resin particle dispersion, preferably the resin particle dispersion containing the amorphous resin A, can be prepared by a known method, but is preferably dispersed by a phase inversion emulsification method, such as a method in which an aqueous medium is added to an organic solvent solution of a resin or a molten resin to perform phase inversion emulsification.
[0065] Examples of the aqueous medium used in the phase inversion emulsification include those described below. The organic solvent used for phase inversion emulsification is not particularly limited as long as it dissolves the resin, but from the viewpoint of facilitating phase inversion, examples include alcohol-based solvents such as ethanol, isopropanol, and isobutanol; ketone-based solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and diethyl ketone; ether-based solvents such as dibutyl ether, tetrahydrofuran, and dioxane; and acetate-based solvents such as ethyl acetate and isopropyl acetate. Among these, from the viewpoint of easy removal from the mixed liquid after addition of the aqueous medium, ketone-based solvents and acetate-based solvents are preferred, and methyl ethyl ketone, ethyl acetate, and isopropyl acetate are more preferred. As an organic solvent for dissolving polyester-based resins, methyl ethyl ketone is preferred, and as an organic solvent for dissolving styrene-acrylic resins, ethyl acetate is preferred. It is preferable to add a neutralizing agent to the organic solvent solution of the polyester resin. Examples of the neutralizing agent include basic substances. Examples of the basic substance include alkali metal hydroxides such as sodium hydroxide and potassium hydroxide, and nitrogen-containing basic substances such as ammonia, trimethylamine, and diethanolamine. The equivalent amount (mol %) of the neutralizing agent used relative to the acid groups of the resin contained in the resin particles is preferably 10 mol % or more, more preferably 30 mol % or more, even more preferably 40 mol % or more, from the viewpoint of obtaining fine resin particles and improving dispersion stability, and is preferably 95 mol % or less, more preferably 90 mol % or less, even more preferably 85 mol % or less. The equivalent amount (mol%) of the neutralizing agent used can be calculated by the following formula: When the equivalent amount of the neutralizing agent used is 100 mol% or less, it is synonymous with the degree of neutralization. Equivalent amount of neutralizing agent used (mol%) = [{weight of neutralizing agent added (g) / equivalent amount of neutralizing agent} / [{weighted average acid value of resin constituting resin particles (mgKOH / g) × weight of resin constituting resin particles (g)} / (56 × 1000)]] × 100
[0066] From the viewpoint of dispersion stability of the resin particle dispersion, it is preferable to add a surfactant to the organic solvent solution of the styrene-acrylic resin. Examples of the surfactant include a nonionic surfactant, an anionic surfactant, and a cationic surfactant. The amount of the surfactant added is preferably 1 part by mass or more, more preferably 2 parts by mass or more, and even more preferably 3 parts by mass or more, and is preferably 20 parts by mass or less, more preferably 10 parts by mass or less, and even more preferably 5 parts by mass or less, relative to 100 parts by mass of the styrene-acrylic resin.
[0067] While stirring the organic solvent solution or the molten resin, the aqueous medium is gradually added to cause phase inversion. From the viewpoint of improving the dispersion stability of the resin particles, the temperature of the organic solvent solution when the aqueous medium is added is preferably not less than the glass transition temperature of the resin constituting the resin particles, more preferably not less than 50°C, even more preferably not less than 60°C, and is preferably not more than 90°C, more preferably not more than 85°C. The content of the amorphous resin A in the resin particles is as described above.
[0068] After the phase inversion emulsification, if necessary, the organic solvent may be removed from the obtained dispersion by distillation, etc. In this case, the amount of the remaining organic solvent in the dispersion is preferably 1% by mass or less, more preferably 0.5% by mass or less, and even more preferably substantially 0% by mass.
[0069] Volume median particle size of resin particles (D 50 From the viewpoint of obtaining a toner that can provide high quality images, the particle size is preferably 0.05 μm or more, more preferably 0.08 μm or more, even more preferably 0.10 μm or more, and is preferably 0.8 μm or less, more preferably 0.4 μm or less, even more preferably 0.3 μm or less. From the viewpoint of obtaining a toner that can provide high quality images, the CV value of the resin particles is preferably 10% or more, more preferably 20% or more, and is preferably 40% or less, more preferably 35% or less. Volume median particle size of resin particles (D 50) and the CV value is determined by the method described in the Examples below.
[0070] From the viewpoint of improving the productivity of the toner and the dispersion stability of the resin particle dispersion, the solid content concentration of the resin particle dispersion is preferably 5% by mass or more, more preferably 10% by mass or more, even more preferably 15% by mass or more, and is preferably 50% by mass or less, more preferably 40% by mass or less, even more preferably 35% by mass or less. The solid content is the total amount of non-volatile components.
[0071] The resin particle dispersion liquid containing the amorphous resin A and the crystalline polyester resin C can be obtained by the same method as described above. When the resin particle dispersion liquid containing the amorphous resin A and the resin particle dispersion liquid containing the crystalline polyester resin C are mixed and used, these resin particle dispersion liquids can be obtained by the same method as described above.
[0072] [Aqueous medium] In the present invention, the aqueous medium is a medium containing water as a main component, and the water content in the aqueous medium is preferably 70% by mass or more, more preferably 80% by mass or more, and even more preferably 90% by mass or more and 100% by mass or less. The water is preferably deionized water or distilled water. Examples of components other than water that can form an aqueous medium together with water include organic solvents that dissolve in water, such as alkyl alcohols having 1 to 5 carbon atoms, dialkyl ketones having 3 to 5 carbon atoms, such as acetone and methyl ethyl ketone, and cyclic ethers, such as tetrahydrofuran. Among these, alkyl alcohols having 1 to 5 carbon atoms are preferred, and methanol or ethanol are more preferred.
[0073] [Colorant Particles] In step 1, it is preferable to aggregate colorant particles containing a colorant together with the resin particles. It is preferable that the colorant particles are mixed with the above-mentioned resin particle dispersion liquid in the form of a colorant particle dispersion liquid in which colorant particles containing a colorant are dispersed in an aqueous medium. As the colorant, any of the dyes, pigments, etc. used as toner colorants can be used. Examples of colorants include carbon black, phthalocyanine blue (e.g., CI Pigment Blue 15:3), permanent brown FG, brilliant fast scarlet, pigment green B, rhodamine-B base, solvent red 49, solvent red 146, solvent blue 35, quinacridone, carmine 6B, and disazo yellow. The toner may be either a black toner or a color toner other than black. From the viewpoint of image density, the content of the colorant in the toner particles is preferably 1% by mass or more, more preferably 2% by mass or more, even more preferably 3% by mass or more, and is preferably 15% by mass or less, more preferably 10% by mass or less, even more preferably 8% by mass or less.
[0074] [Method for producing colorant particle dispersion] The colorant particles are preferably obtained as a colorant particle dispersion by dispersing a colorant and an aqueous medium using a dispersing machine such as a homogenizer, an ultrasonic dispersing machine, etc. From the viewpoint of improving the dispersion stability of the colorant, the dispersion is preferably carried out in the presence of a surfactant or an addition polymer (hereinafter, the addition polymer used to disperse the colorant is also referred to as "addition polymer E"). Examples of the surfactant include a nonionic surfactant, an anionic surfactant, and a cationic surfactant. The addition polymer E preferably has a constituent unit derived from an addition polymerizable monomer a having an aromatic group, and further preferably contains at least one selected from the group consisting of an addition polymerizable monomer b having an ionic group, an addition polymerizable monomer c having a polyalkylene oxide group, and a macromonomer d. For the colorant particle dispersion using the addition polymer E, see JP2021-026129A.
[0075] From the viewpoint of image density of the printed matter, the content of the colorant in the colorant particle dispersion is preferably 1% by mass or more, more preferably 3% by mass or more, even more preferably 5% by mass or more, and is preferably 40% by mass or less, more preferably 30% by mass or less, even more preferably 20% by mass or less. The solids concentration of the colorant particle dispersion is preferably 5% by mass or more, more preferably 10% by mass or more, even more preferably 15% by mass or more, and is preferably 40% by mass or less, more preferably 30% by mass or less.
[0076] Volume median particle size D of colorant particles 50 From the viewpoint of improving the dispersibility of the colorant in the toner, the particle size is preferably 0.05 μm or more, more preferably 0.08 μm or more, and is preferably 0.4 μm or less, more preferably 0.3 μm or less, and further preferably 0.25 μm or less. From the viewpoint of improving the dispersibility of the colorant in the toner, the CV value of the colorant particles is preferably 10% or more, more preferably 15% or more, and is preferably 40% or less, more preferably 35% or less, and even more preferably 30% or less. Volume median particle size D of colorant particles 50 and CV values are measured by the methods in the Examples.
[0077] [Release agent particles] In step 1, it is preferable to aggregate release agent particles containing a release agent together with the resin particles and the colorant particles. The release agent particles are preferably mixed with the above-mentioned resin particle dispersion liquid in the form of a release agent particle dispersion liquid in which release agent particles containing a release agent are dispersed in an aqueous medium. Examples of the release agent include polypropylene wax, polyethylene wax, ethylene propylene copolymer wax, hydrocarbon waxes such as microcrystalline wax, paraffin wax, Fischer-Tropsch wax, and oxides thereof, ester waxes such as carnauba wax, montan wax, and deacidified waxes thereof, and fatty acid ester wax, fatty acid amides, fatty acids, higher alcohols, and fatty acid metal salts. These may be used alone or in combination.
[0078] The melting point of the release agent is preferably 60° C. or higher, more preferably 70° C. or higher, and preferably 160° C. or lower, more preferably 140° C. or lower, even more preferably 120° C. or lower, and even more preferably 100° C. or lower.
[0079] The content of the release agent in the toner particles is preferably 0.1% by mass or more, more preferably 1% by mass or more, even more preferably 5% by mass or more, and is preferably 20% by mass or less, more preferably 15% by mass or less.
[0080] [Method for producing release agent particle dispersion liquid] The release agent particle dispersion can be obtained by using a surfactant, but is preferably obtained by mixing the release agent and resin particles. By preparing the release agent particles using the release agent and resin particles, the release agent particles are stabilized by the resin constituting the resin particles, and it becomes possible to disperse the release agent in an aqueous medium without using a surfactant. It is considered that the release agent particle dispersion has a structure in which a large number of resin particles are attached to the surface of the release agent particles. The resin constituting the resin particles in which the release agent is dispersed is preferably a polyester resin, and the above-mentioned amorphous polyester resin is more preferable. In addition, a composite resin D having a polyester resin segment and an addition polymerization resin segment may be used. For the composite resin D, JP 2021-182045 A is referred to.
[0081] Volume median particle size D of release agent particles 50 From the viewpoint of obtaining uniform aggregated particles 1 by aggregation, the average particle size is preferably 0.05 μm or more, more preferably 0.1 μm or more, even more preferably 0.2 μm or more, and is preferably 1 μm or less, more preferably 0.8 μm or less, even more preferably 0.6 μm or less. The CV value of the release agent particles is preferably 10% or more, more preferably 15% or more, and is preferably 45% or less, more preferably 40% or less. Volume median particle size D of release agent particles 50The CV value is measured by the method described in the Examples.
[0082] Aggregated particles 1 may also contain additives such as charge control agents, magnetic powders, flowability improvers, conductivity adjusters, reinforcing fillers such as fibrous substances, antioxidants, antiaging agents, and cleaning improvers.
[0083] [Surfactant] In step 1, the resin particles are preferably aggregated after preparing a mixed dispersion by mixing a resin particle dispersion, and, if necessary, a colorant particle dispersion and a release agent particle dispersion. When preparing the mixed dispersion, the preparation may be carried out in the presence of a surfactant in order to improve the dispersion stability of the resin particles and optional components such as colorant particles and release agent particles that are added as necessary. Examples of the surfactant include anionic surfactants such as alkylbenzene sulfonates and alkyl ether sulfates; and nonionic surfactants such as polyoxyethylene alkyl ethers and polyoxyethylene alkenyl ethers. One or more types of surfactants may be used. When a surfactant is used, the amount of the surfactant used is, in terms of the total amount of the surfactant, preferably 0.1 parts by mass or more, more preferably 0.5 parts by mass or more, and preferably 10 parts by mass or less, more preferably 5 parts by mass or less, per 100 parts by mass of the resin particles.
[0084] The resin particle dispersion and the optional components are mixed by a conventional method. From the viewpoint of efficient aggregation, it is preferable to add an aggregating agent to the mixed dispersion obtained by the mixing.
[0085] [Flocculant] Examples of the flocculant include organic flocculants such as quaternary salt cationic surfactants and polyethyleneimine; inorganic metal salts such as sodium sulfate, sodium nitrate, sodium chloride, calcium chloride, calcium nitrate; inorganic ammonium salts such as ammonium sulfate, ammonium chloride, ammonium nitrate; and inorganic agents such as divalent or higher metal complexes. From the viewpoint of improving the flocculation property and obtaining uniform flocculated particles 1, inorganic flocculants having a valence of 1 to 5 are preferred, inorganic metal salts having a valence of 1 to 2 and inorganic ammonium salts having a valence of 1 to 2 are more preferred, and ammonium sulfate is even more preferred.
[0086] For example, 5 to 50 parts by mass of the aggregating agent is added to a mixed dispersion liquid containing resin particles, release agent particles, and colorant particles and having a temperature of 0° C. or higher and 40° C. or lower, relative to 100 parts by mass of the resin particles, and the resin particles, release agent particles, and colorant particles are aggregated in an aqueous medium to obtain aggregated particles 1. Furthermore, from the viewpoint of promoting aggregation, it is preferable to increase the temperature of the dispersion liquid after adding the aggregating agent.
[0087] Volume median particle size D of aggregated particles 1 obtained in step 1 50 is preferably 3 μm or more, more preferably 4 μm or more, even more preferably 5 μm or more, and is preferably 10 μm or less, more preferably 8 μm or less, even more preferably 7 μm or less. It is preferable to continue the aggregation until a desired volume median particle size is reached to obtain aggregated particles 1.
[0088] In the production method of the present invention, in order to obtain toner particles having a core-shell structure, in step 1, the obtained aggregated particles 1 may be used as cores, and shell resin particles containing an amorphous resin may be attached and aggregated to obtain aggregated particles 2 having a core-shell structure. As the shell resin particles, the amorphous resin A can be preferably used. The shell resin particle dispersion liquid can be obtained by the same method as the above-mentioned method for producing the resin particle dispersion liquid. In addition, in the case where the shell resin particles are aggregated in step 1 of the production method of the present invention, it is preferable to proceed to step 2 when aggregated particles 2 have grown to a particle size appropriate for toner particles. The mass ratio of the shell resin particles to the mass of the aggregated particles 1 [shell resin particles / aggregated particles 1] is, from the viewpoint of low-temperature fixing property of the toner, preferably 1 / 99 or more, more preferably 3 / 97 or more, even more preferably 5 / 95 or more, and is preferably 20 / 80 or less, more preferably 15 / 85 or less, even more preferably 10 / 90 or less.
[0089] <Process 2> In step 2, a water-soluble addition polymer (water-soluble addition polymer F) of an aromatic group-containing monomer and a hydrophilic monomer is added to the aggregated particles obtained in step 1 in an amount of 0.2 parts by mass to 30 parts by mass relative to 100 parts by mass of the binder resin in the aggregated particles, and then the temperature is raised to fuse the particles, thereby obtaining fused particles. In step 2, it is preferable to add an aqueous solution of the water-soluble addition polymer F. The water-soluble addition polymer F is added for the purpose of improving the dispersion stability of the aggregated particles during fusion.
[0090] [Water-soluble addition polymer F] The water-soluble addition polymer F is obtained by addition polymerization of an aromatic group-containing monomer and a hydrophilic monomer. The water-soluble addition polymer F may contain a structural unit derived from a hydrophobic monomer.
[0091] The aromatic group-containing monomer is a vinyl monomer having an aromatic group having 6 to 22 carbon atoms which may have a substituent containing a hetero atom, and is more preferably one or more selected from a styrene-based monomer and an aromatic group-containing (meth)acrylate. The molecular weight of the aromatic group-containing monomer is preferably less than 500. Examples of the styrene monomer include styrene, α-methylstyrene, 2-methylstyrene, etc., and examples of the aromatic group-containing (meth)acrylate include benzyl (meth)acrylate, phenoxyethyl (meth)acrylate, etc. Among these, preferred are styrene, α-methylstyrene, and benzyl (meth)acrylate, and more preferred are styrene, α-methylstyrene, and benzyl (meth)acrylate. The styrene-based monomer may be used alone or in combination of two or more kinds.
[0092] Examples of the hydrophilic monomer include a monomer having an ionic functional group and a non-ionic hydrophilic monomer having no ionic functional group, and preferably a monomer having an ionic functional group. Examples of monomers having an ionic functional group include monomers having a cationic group and monomers having an anionic group. From the viewpoint of improving the dispersion stability of aggregated particles and reducing the content of coarse particles in the toner obtained, monomers having an anionic group are preferred. As the anionic group, a carboxy group (-COOM 1 ), sulfonic acid group (-SO 3 M 1 ), phosphate group (-OPO 3 M 1 2 ) which exhibits acidity by dissociating and releasing hydrogen ions, and from the viewpoint of improving the dispersion stability of aggregated particles and reducing the content of coarse particles in the toner obtained, a carboxy group is preferred. 1 represents a hydrogen atom, an alkali metal, ammonium or an organic ammonium. The anionic group may be in a dissociated form (e.g., -COO - , -SO 3 - , -OPO 3 2- , -OPO 3 - M 1 ) shall be included. Examples of the monomer having a carboxy group include (meth)acrylic acid, crotonic acid, itaconic acid, maleic acid, fumaric acid, citraconic acid, and 2-methacryloyloxymethylsuccinic acid, with (meth)acrylic acid being preferred. Examples of monomers having a sulfonic acid group include styrenesulfonic acid, 2-acrylamido-2-methylpropanesulfonic acid, and 3-sulfopropyl(meth)acrylate. Examples of monomers having a phosphoric acid group include vinylphosphonic acid, vinyl phosphate, bis(methacryloxyethyl) phosphate, diphenyl-2-acryloyloxyethyl phosphate, and diphenyl-2-methacryloyloxyethyl phosphate. Among these, preferred is a monomer having a carboxy group, more preferred is at least one selected from (meth)acrylic acid, crotonic acid, itaconic acid, maleic acid, fumaric acid, citraconic acid and 2-methacryloyloxymethylsuccinic acid, and even more preferred is (meth)acrylic acid.
[0093] Examples of nonionic hydrophilic monomers include hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate and 3-hydroxypropyl (meth)acrylate; polyalkylene glycol (meth)acrylates such as polyethylene glycol (n=2 to 30, n indicates the average number of moles of oxyethylene groups added. Hereinafter, n indicates the average number of moles of the oxyalkylene groups added.) (meth)acrylate; alkoxypolyalkylene glycol (meth)acrylates such as methoxypolyethylene glycol (n=1 to 30) (meth)acrylate; and phenoxy (ethylene glycol / propylene glycol copolymer) (n=1 to 30, ethylene glycol therein: n=1 to 29) (meth)acrylate.
[0094] Specific examples of commercially available nonionic hydrophilic monomers include NK Ester M-40G, 90G, 230G, etc. (all trade names of Shin-Nakamura Chemical Co., Ltd.), Blemmer PE-90, 200, 350, etc., Blemmer PME-100, 200, 400, etc., Blemmer 50PEP-300, Blemmer 50POEP-800B, etc. (all trade names of NOF Corporation). The hydrophilic monomers may be used alone or in combination of two or more.
[0095] The hydrophobic monomer is preferably a (meth)acrylic acid ester having a hydrocarbon group derived from an aliphatic alcohol. The (meth)acrylic acid ester having a hydrocarbon group derived from an aliphatic alcohol is preferably one having a hydrocarbon group derived from an aliphatic alcohol having 1 to 22 carbon atoms. Examples thereof include (meth)acrylic acid esters having an alkyl group such as methyl (meth)acrylate, ethyl (meth)acrylate, (iso)propyl (meth)acrylate, (iso or tertiary)butyl (meth)acrylate, (iso)amyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, (iso)octyl (meth)acrylate, (iso)decyl (meth)acrylate, (iso)dodecyl (meth)acrylate, (iso)stearyl (meth)acrylate, and cyclohexyl (meth)acrylate. Among these, more preferred are those having an alkyl group having 1 to 10 carbon atoms, even more preferred are those having an alkyl group having 1 to 8 carbon atoms, even more preferred are methyl (meth)acrylate and (iso or tertiary)butyl (meth)acrylate, and particularly preferred are methyl methacrylate and n-butyl acrylate. Incidentally, aromatic group-containing monomers are not included in the hydrophobic monomers.
[0096] The contents of aromatic group-containing monomers, hydrophilic monomers and hydrophobic monomers in the raw material monomer mixture (content as unneutralized amounts; the same applies below) during production of the water-soluble addition polymer F, or the contents of aromatic group-containing monomer-derived constituent units, hydrophilic monomer-derived constituent units and hydrophobic monomer-derived constituent units in the water-soluble addition polymer F, are as follows, from the viewpoint of improving the dispersion stability of the agglomerated particles. The content of the aromatic group-containing monomer component in the raw material monomer mixture is preferably 10% by mass or more, more preferably 15% by mass or more, even more preferably 20% by mass or more, and is preferably 95% by mass or less, more preferably 90% by mass or less, even more preferably 80% by mass or less. The content of the aromatic group-containing monomer-derived constituent units in the water-soluble addition polymer F is the same as the content of the aromatic group-containing monomer component in the raw material monomer mixture. The content of the hydrophilic monomer component in the raw material monomer mixture is preferably 5% by mass or more, more preferably 7% by mass or more, and preferably 70% by mass or less, more preferably 65% by mass or less, and even more preferably 60% by mass or less. The content of the constitutional units derived from hydrophilic monomers in the water-soluble addition polymer F is the same as the content of the hydrophilic monomer component in the raw material monomer mixture. When the raw material monomer mixture contains a hydrophobic monomer component, the content of the hydrophobic monomer component in the raw material monomer mixture is preferably 5% by mass or more, more preferably 20% by mass or more, even more preferably 50% by mass or more, and preferably 85% by mass or less, more preferably 80% by mass or less, even more preferably 75% by mass or less. When the water-soluble addition polymer F contains a constitutional unit derived from a hydrophobic monomer, the content of the constitutional unit derived from a hydrophobic monomer in the water-soluble addition polymer F is the same as the content of the hydrophobic monomer component in the raw material monomer mixture. The total of the content of the aromatic group-containing monomer component, the content of the hydrophilic monomer component, and the content of the hydrophobic monomer component is 100% by mass.
[0097] The mass ratio of [hydrophilic monomer component / aromatic group-containing monomer component] is preferably 0.06 or more, more preferably 0.20 or more, even more preferably 0.35 or more, and is preferably 14 or less, more preferably 10 or less, even more preferably 5 or less, even more preferably 1.5 or less, even more preferably 1 or less.
[0098] [Method for producing water-soluble addition polymer F] The water-soluble addition polymer F is produced by copolymerizing the raw material monomer mixture by a known polymerization method such as bulk polymerization, solution polymerization, suspension polymerization, emulsion polymerization, etc. Among these polymerization methods, the solution polymerization method is preferred. The solvent used in the solution polymerization method is not particularly limited, but a polar organic solvent is preferred. When the polar organic solvent has water miscibility, it can be used by mixing with water. Examples of the polar organic solvent include aliphatic alcohols having 1 to 3 carbon atoms, ketones having 3 to 5 carbon atoms, ethers, esters such as ethyl acetate, etc. Among these, methanol, ethanol, acetone, methyl ethyl ketone (MEK), or a mixed solvent of one or more of these with water is preferred, ethanol, methyl ethyl ketone, or a mixed solvent of these with water is preferred, and a mixed solvent of methyl ethyl ketone or ethanol with water is preferred. In the polymerization, a polymerization initiator and a polymerization chain transfer agent can be used. As the polymerization initiator, known radical polymerization initiators such as azo compounds such as 2,2'-azobisisobutyronitrile, 4,4'-azobis(4-cyanovaleric acid), 2,2'-azobis(2,4-dimethylvaleronitrile), and organic peroxides such as t-butyl peroxyoctoate and benzoyl peroxide can be used. The polymerization initiator may be used alone or in combination of two or more. The amount of the radical polymerization initiator added is preferably 0.001 parts by mass or more and 5 parts by mass or less, more preferably 0.01 parts by mass or more and 3 parts by mass or less, per 100 parts by mass of the raw material monomer mixture. As the polymerization chain transfer agent, known chain transfer agents such as carboxyl group-containing mercaptans such as mercaptoacetic acid, 2-mercaptopropionic acid, 3-mercaptopropionic acid, and mercaptosuccinic acid; alkyl mercaptans such as butanethiol, octanethiol, decanethiol, dodecanethiol, hexadecanethiol, and octadecanethiol; hydroxyl group-containing mercaptans such as 2-mercaptoethanol and 3-mercapto-1,2-propanediol; and thiuram disulfides can be used. One type of polymerization chain transfer agent may be used alone, or two or more types may be used in combination. The amount of the polymerization chain transfer agent added is preferably 0.1 parts by mass or more and 20 parts by mass or less, more preferably 0.3 parts by mass or more and 10 parts by mass or less, per 100 parts by mass of the raw material monomer mixture. Furthermore, there is no limitation on the chain form of the polymerized monomers, and any of the polymerization forms such as random, block, and graft may be used.
[0099] Preferred polymerization conditions vary depending on the type of polymerization initiator, monomer, solvent, etc. used, but usually, the polymerization temperature is preferably 30° C. or higher, more preferably 50° C. or higher, and preferably 95° C. or lower, more preferably 80° C. or lower. The polymerization time is preferably 1 hour or longer, more preferably 2 hours or longer, and preferably 20 hours or shorter, more preferably 10 hours or shorter. The polymerization atmosphere is preferably a nitrogen gas atmosphere, an inert gas atmosphere such as argon, etc. After the polymerization reaction is completed, the produced polymer can be isolated from the reaction solution by a known method such as reprecipitation, solvent distillation, etc. The obtained polymer can also be purified by removing unreacted monomers, etc., by reprecipitation, membrane separation, chromatography, extraction, etc.
[0100] When the hydrophilic monomer contains a monomer having an anionic group, the acid value of the water-soluble addition polymer F is, from the viewpoint of improving the dispersion stability of the aggregated particles, preferably 50 mgKOH / g or more, more preferably 70 mgKOH / g or more, even more preferably 100 mgKOH / g or more, even more preferably 150 mgKOH / g or more, and is preferably 500 mgKOH / g or less, more preferably 450 mgKOH / g or less, even more preferably 400 mgKOH / g or less. The acid value of the water-soluble addition polymer F can be measured by the method described in the Examples (method of measuring "acid value of resin").
[0101] From the viewpoint of improving the dispersion stability of aggregated particles, the weight average molecular weight of the water-soluble addition polymer F is preferably 1,000 or more, more preferably 5,000 or more, even more preferably 9,000 or more, and is preferably 100,000 or less, more preferably 80,000 or less, even more preferably 60,000 or less. The weight average molecular weight can be measured by the method described in the Examples.
[0102] The amount of water-soluble addition polymer F added in step 2 is, relative to 100 parts by weight of the binder resin in the aggregated particles, from the viewpoints of improving the dispersion stability of the aggregated particles and reducing the content of coarse particles in the toner obtained, 0.2 parts by weight or more, preferably 0.4 parts by weight or more, more preferably 0.8 parts by weight or more, and even more preferably 2 parts by weight or more, and, from the viewpoint of suppressing a decrease in the charge amount of the toner under high temperature and high humidity conditions, is 30 parts by weight or less, more preferably 25 parts by weight or less, even more preferably 15 parts by weight or less, and even more preferably 5 parts by weight or less.
[0103] In step 2, the particles in the aggregate that were primarily physically attached to each other are fused together to form toner particles. As described above, in step 2, it is preferable to add an aqueous solution of the water-soluble addition polymer F to the aggregated particles obtained in step 1.
[0104] The water-soluble addition polymer F has an acid group (e.g., -COOH, -SO3 H, -OPO 3 H 2 ), at least a part of the acid groups is preferably neutralized with a neutralizing agent from the viewpoint of improving the dispersion stability of the aggregated particles. Examples of the neutralizing agent include bases such as lithium hydroxide, sodium hydroxide, potassium hydroxide, ammonia, various amines, etc., and preferably sodium hydroxide. The water-soluble addition polymer F may be neutralized in advance. From the viewpoint of improving the dispersion stability of the aggregated particles, the amount of the neutralizing agent used is preferably 10 mol % or more, more preferably 30 mol % or more, even more preferably 50 mol % or more, and even more preferably 70 mol % or more, and is 100 mol % or less. The equivalent amount of the neutralizing agent used can be calculated by the following formula. Equivalent amount of neutralizing agent used (mol%) = [{weight of neutralizing agent added (g) / equivalent amount of neutralizing agent} / [{acid value of water-soluble addition polymer F (mg KOH / g) × weight of water-soluble addition polymer F (g)} / (56 × 1,000)]] × 100
[0105] In step 2, the temperature is maintained at or above the glass transition temperature of the amorphous resin A in order to improve the fusion property of the aggregated particles. From the viewpoint of improving the fusion properties of the aggregated particles and improving the productivity of the toner, the holding temperature in the fusion step is preferably at least 2° C. higher than the glass transition temperature of amorphous resin A, more preferably at least 3° C. higher, and even more preferably at least 5° C. higher, and is preferably not more than 30° C. higher, more preferably not more than 25° C. higher, and even more preferably not more than 20° C. higher than the glass transition temperature of amorphous resin A. In this case, the time for which the toner is maintained at a temperature equal to or higher than the glass transition temperature of the amorphous resin A is, from the viewpoint of low-temperature fixability of the toner, preferably 1 minute or more, more preferably 10 minutes or more, even more preferably 30 minutes or more, and is preferably 240 minutes or less, more preferably 180 minutes or less, even more preferably 120 minutes or less, even more preferably 90 minutes or less. It is preferable to maintain the temperature at the above temperature until the desired circularity is achieved.
[0106] The volume median particle size (D 50 From the viewpoint of versatility of the toner, the particle size is preferably 3 μm or more, more preferably 4 μm or more, even more preferably 5 μm or more, and is preferably 10 μm or less, more preferably 8 μm or less, even more preferably 7 μm or less. The volume median particle size of the fused particles obtained in step 2 is preferably equal to or smaller than the volume median particle size of the aggregated particles. That is, in step 2, it is preferable that aggregation and fusion between the aggregated particles does not occur.
[0107] <Post-processing process> In the production method of the present invention, a post-treatment step may be carried out after step 2, and it is preferable to obtain toner particles by isolation. Since the fused particles obtained in step 2 are present in an aqueous medium, it is preferable to first carry out solid-liquid separation. For solid-liquid separation, a suction filtration method or the like is preferably used. It is preferable to wash after the solid-liquid separation. At this time, it is preferable to remove the added surfactant, etc., so that, in the case where the surfactant has a cloud point, washing with an aqueous medium at a temperature below the cloud point of the surfactant is preferable. It is preferable to wash multiple times.
[0108] Next, drying is preferably performed. The temperature during drying is preferably set so that the temperature of the fused particles themselves is lower than the glass transition temperature of the amorphous resin A, and more preferably 10° C. or more lower. As the drying method, a vacuum low-temperature drying method, a vibration-type fluidized drying method, a spray drying method, a freeze drying method, a flash jet method, or the like is preferably used.
[0109] [Toner Particles] The toner particles obtained by drying or the like can be used as they are as a toner for developing electrostatic images, but it is preferable to use the toner particles after surface treatment as described later as a toner for developing electrostatic images. The volume median particle size of toner particles (D 50From the viewpoint of improving the productivity and low-temperature fixability of the toner, the particle diameter is preferably 2 μm or more, more preferably 3 μm or more, even more preferably 4 μm or more, and is preferably 10 μm or less, more preferably 8 μm or less, even more preferably 7 μm or less. The CV value of the toner particles is preferably 12% or more, more preferably 14% or more, and even more preferably 16% or more, from the viewpoint of improving the productivity of the toner, and is preferably 40% or less, more preferably 35% or less, from the viewpoint of obtaining high-quality images. From the viewpoint of obtaining a high quality image, the circularity of the toner particles is preferably 0.955 or more, more preferably 0.960 or more, even more preferably 0.965 or more, and is preferably 0.990 or less, more preferably 0.985 or less, even more preferably 0.980 or less.
[0110] <External additives> The toner particles can be used as they are, but it is preferable to use the toner after adding a fluidizing agent or the like as an external additive to the surface of the toner particles. Examples of the external additive include inorganic fine particles such as hydrophobic silica, titanium oxide fine particles, alumina fine particles, cerium oxide fine particles, and carbon black, and polymer fine particles such as polycarbonate, polymethyl methacrylate, and silicone resin. Of these, hydrophobic silica is preferred. The external additives may be used alone or in combination of two or more kinds. Also, external additives of the same kind but different particle diameters may be used in combination. When the toner particles are surface-treated using an external additive, the amount of the external additive added is, relative to 100 parts by mass of the toner particles, preferably 1 part by mass or more, more preferably 2 parts by mass or more, even more preferably 3 parts by mass or more, and preferably 5 parts by mass or less, more preferably 4.5 parts by mass or less, even more preferably 4 parts by mass or less.
[0111] [Toner for developing electrostatic images] The toner for developing electrostatic images obtained according to the present invention can be used as a one-component developer, or mixed with a carrier to form a two-component developer. EXAMPLES
[0112] The present invention will be described in more detail below with reference to examples, etc. In the following examples, the physical properties were measured and evaluated by the following methods.
[0113] [measurement] [Acid value of resin] Measurements were performed in accordance with JIS K0070: 1992, except that the measurement solvent was a mixed solvent of acetone and toluene (acetone:toluene=1:1 (volume ratio)).
[0114] [Softening point, crystallinity index, melting point and glass transition temperature of resin] (1) Softening point Using a flow tester "CFT-500D" (Shimadzu Corporation), 1 g of sample was heated at a temperature increase rate of 6°C / min, while applying a load of 1.96 MPa with the plunger, and extruding the sample from a nozzle with a diameter of 1 mm and a length of 1 mm. The plunger descent amount of the flow tester was plotted against the temperature, and the temperature at which half of the sample flowed out was taken as the softening point. (2) Crystallinity index Using a differential scanning calorimeter "Q100" (manufactured by TA Instruments Japan Co., Ltd.), 0.02 g of sample was weighed into an aluminum pan and cooled to 0°C at a rate of 10°C / min. The sample was then left to stand for 1 minute, after which it was heated to 180°C at a rate of 10°C / min and the calorific value was measured. The temperature of the peak with the largest peak area among the observed endothermic peaks was taken as the endothermic maximum peak temperature (1), and the crystallinity index was calculated by (softening point (°C)) / (endothermic maximum peak temperature (1) (°C)). (3) Melting point and glass transition temperature Using a differential scanning calorimeter "Q100" (manufactured by TA Instruments Japan Co., Ltd.), 0.02 g of the sample was weighed into an aluminum pan, heated to 200°C, and cooled from that temperature to 0°C at a rate of 10°C / min. The sample was then heated at a rate of 10°C / min, and the calorific value was measured. Among the endothermic peaks observed, the temperature of the peak with the largest peak area was taken as the maximum endothermic peak temperature (2). In the case of a crystalline resin, this peak temperature was taken as the melting point. In the case of an amorphous resin, when a peak was observed, the temperature of the peak was taken as the glass transition temperature. When no peak was observed but a step was observed, the temperature at the intersection of the tangent showing the maximum slope of the curve at the step and an extension of the baseline on the low temperature side of the step was taken as the glass transition temperature.
[0115] [Weight average molecular weight (Mw) of water-soluble addition polymer] The measurement was performed by gel permeation chromatography (Tosoh Corporation, GPC apparatus (HLC-8320GPC), Tosoh Corporation columns (TSKgel SuperAWM-H, TSKgel SuperAW3000, TSKgel guardcolum Super AW-H), flow rate: 0.5mL / min) using a solution of phosphoric acid and lithium bromide dissolved in N,N-dimethylformamide to a concentration of 43mmol / L and 50mmol / L, respectively, as an eluent, and using a monodisperse polystyrene kit with known molecular weight (PStQuick B (F-550, F-80, F-10, F-1, A-1000), PStQuick C (F-288, F-40, F-4, A-5000, A-500), Tosoh Corporation) as a standard substance. The measurement sample was prepared by mixing 0.1 g of polymer with 10 mL of the eluent in a glass vial, stirring with a magnetic stirrer at 25° C. for 10 hours, and filtering with a syringe filter (DISMIC-13HP PTFE 0.2 μm, manufactured by ADVANTEC).
[0116] [Melting point of release agent] Using a differential scanning calorimeter "Q100" (manufactured by TA Instruments Japan Co., Ltd.), 0.02 g of the sample was weighed into an aluminum pan, heated to 200°C, and then cooled from 200°C to 0°C at a rate of 10°C / min. The sample was then heated at a rate of 10°C / min, the calorific value was measured, and the maximum endothermic peak temperature was taken as the melting point.
[0117] [Volume median particle diameter D of resin particles, colorant particles, and release agent particles 50 and CV value] (1) Measuring device: Laser diffraction type particle size measuring device "LA-920" (manufactured by Horiba Ltd.) (2) Measurement conditions: Put the sample dispersion in a measurement cell, add distilled water, and measure the volume median particle size D at a concentration where the absorbance is in the appropriate range. 50 and volume average particle size D v The CV value was calculated according to the following formula: CV value (%) = (Standard deviation of particle size distribution / Volume average particle size D v ) x 100
[0118] [Solid Content Concentration of Resin Particle Dispersion, Colorant Particle Dispersion, and Release Agent Particle Dispersion] Using an infrared moisture meter "FD-230" (Kett Electric Laboratory Co., Ltd.), the moisture content (mass%) of 5 g of the measurement sample was measured at a drying temperature of 150°C and measurement mode 96 (monitoring time 2.5 minutes, moisture content fluctuation range 0.05%). The solid content concentration was calculated according to the following formula. Solid concentration (mass%) = 100-moisture (mass%)
[0119] [Volume median particle diameter of agglomerated particles D 50 〕 Volume median particle size of agglomerated particles D 50 was measured as follows: Measuring instrument: "Coulter Multisizer (registered trademark) III" (manufactured by Beckman Coulter, Inc.) Aperture diameter: 50μm Analysis software: "Multisizer (registered trademark) III version 3.51" (Beckman Coulter, Inc.) Electrolyte: "Isoton (registered trademark) II" (manufactured by Beckman Coulter, Inc.) Measurement conditions: The sample dispersion is added to 100 mL of the electrolyte to adjust the concentration so that the particle size of 30,000 particles can be measured in 20 seconds. Then, 30,000 particles are measured again, and the volume median particle size D is calculated from the particle size distribution. 50 asked for.
[0120] [Circularity of fused particles] The circularity of the fused particles was measured under the following conditions. Measurement equipment: Flow-type particle image analyzer "FPIA-3000" (Sysmex Corporation) Preparation of dispersion: A dispersion of fused particles was prepared by diluting with deionized water to a solids concentration of 0.001 to 0.05% by mass. Measurement mode: HPF measurement mode
[0121] [Volume median particle size of toner particles D 50 and CV value] Volume median particle size of toner particles D 50 was measured as follows: The measurement device, aperture diameter, analysis software, and electrolyte were determined based on the volume median particle diameter D 50 The same one used in the measurement was used. Dispersion: Polyoxyethylene lauryl ether "EMULGEN (registered trademark) 109P" (manufactured by Kao Corporation, HLB (hydrophile-lipophile balance) = 13.6) was dissolved in the electrolyte to obtain a dispersion with a concentration of 5 mass %. Dispersion conditions: 10 mg of a measurement sample of dried toner particles was added to 5 mL of the dispersion liquid, and dispersed for 1 minute using an ultrasonic disperser. Thereafter, 25 mL of the electrolyte was added, and the mixture was further dispersed for 1 minute using an ultrasonic disperser to prepare a sample dispersion liquid. Measurement conditions: The sample dispersion is added to 100 mL of the electrolyte to adjust the concentration so that the particle size of 30,000 particles can be measured in 20 seconds. Then, 30,000 particles are measured and the volume median particle size D is calculated from the particle size distribution. 50 and volume average particle size D V asked for. The CV value (%) was calculated according to the following formula. CV value (%) = (Standard deviation of particle size distribution / Volume average particle size D V ) x 100
[0122] [Resin manufacturing] Production Example A1 (Production of Resin A-1) A 10L four-neck flask equipped with a thermometer, a stainless steel stirring rod, a dehydration tube, a cooling tube, and a nitrogen inlet tube was charged with neopentyl glycol, terephthalic acid, and an esterification catalyst shown in Table 1, and the mixture was heated to 180°C in a mantle heater in a nitrogen atmosphere, reacted for 2 hours, and then heated stepwise to 210°C at a rate of 5°C / h. After cooling to 180°C, isophthalic acid was added, the mixture was heated again to 190°C, reacted for 1 hour, and then heated stepwise to 220°C at a rate of 10°C / h. The mixture was then reacted at 13.3kPa until the desired softening point was obtained, and an amorphous polyester resin (resin A-1) was obtained. The physical properties are shown in Table 1.
[0123] Manufacturing Example A31 (Manufacturing of Resin A-31) The raw material monomers of polyester resin other than isophthalic acid shown in Table 1, and the esterification catalyst were placed in a 10L four-neck flask equipped with a nitrogen inlet tube, a dehydration tube, a stirrer, and a thermocouple. Under a nitrogen atmosphere, the reaction system was held at 205°C for 1 hour, then heated from 205°C to 235°C at 10°C / h, and then held at 235°C for 3 hours to perform polycondensation. After that, it was cooled to 185°C, and isophthalic acid was added to the reaction system, heated from 185°C to 235°C at 10°C / h, and reacted at 235°C for 5 hours, and reacted at 235°C and 10kPa until the softening point shown in Table 1 was reached, to obtain resin A-31. The physical properties of resin A-31 are shown in Table 1.
[0124] Production Example A2 (Production of Resin A-2) The raw material monomers of polyester resin other than trimellitic anhydride shown in Table 1, and the esterification catalyst were placed in a 10L four-neck flask equipped with a nitrogen inlet tube, a dehydration tube, a stirrer, and a thermocouple. The temperature was raised to 235°C while stirring under a nitrogen atmosphere, and after maintaining at 235°C for 6 hours, the pressure in the flask was further reduced and maintained at 8.3kPa for 1 hour. After that, it was cooled to 215°C and returned to atmospheric pressure, and then trimellitic anhydride was added and maintained at 215°C for 1 hour, and the pressure in the flask was further reduced and the reaction was continued at 8.3kPa until the desired softening point was reached, to obtain an amorphous polyester resin (resin A-2). The physical properties are shown in Table 1.
[0125] Manufacturing Example A3 (Manufacturing of Resin A-3) The raw material monomers of the polyester resin segment other than fumaric acid shown in Table 1 were placed in a 10L four-neck flask equipped with a dehydration tube equipped with a nitrogen inlet tube, a stirrer and a thermocouple, and the reaction system was heated to 160°C under a nitrogen atmosphere. Then, a mixture of the bireactive monomer, the raw material monomers of the addition polymerization resin segment and dibutyl peroxide was dropped into the reaction system over 1 hour using a dropping funnel. After the dropping, the addition polymerization reaction was allowed to proceed for 1 hour while maintaining the temperature at 160°C. Then, the reaction system was raised to 200°C and reacted for 1 hour under a reduced pressure of 8.0 kPa, and then the esterification catalyst and esterification promoter shown in Table 1 were added to the reaction system, followed by polycondensation reaction at 235°C for 6 hours, and further reaction at 235°C and 8.0 kPa for 1 hour. After cooling the reaction system to 180°C, fumaric acid and a radical polymerization inhibitor (4-tert-butylcatechol) were added to the reaction system, and the temperature was raised from 180°C to 210°C at a rate of 10°C / h, and the reaction was carried out at 210°C for 1 hour, and then the reaction was carried out at 210°C and 10 kPa until the softening point shown in Table 1 was reached, to obtain a composite resin (Resin A-3). The physical properties are shown in Table 1.
[0126] Manufacturing Example A4 (Manufacturing of Resin A-4) 400g of xylene was placed in a 3L four-neck flask equipped with a thermometer, a stainless steel stirring rod, a flow-down condenser, a dropping funnel and a nitrogen inlet tube, and 902g of styrene, 198g of n-butyl acrylate and 110g of dibutyl peroxide as a radical polymerization initiator were placed in the dropping funnel. Under a nitrogen atmosphere, the xylene was heated to 135°C while stirring, and the mixture in the dropping funnel was dropped over 1 hour. After that, the temperature was raised to 160°C and held at 160°C for 2 hours, after which the pressure in the flask was further reduced and held at 8kPa for 1 hour, and xylene was removed at 200°C to obtain Resin A-4. The physical properties of the obtained Resin A-4 were a softening point of 106°C, a glass transition temperature of 53°C and a crystallinity index of 1.7.
[0127] [Table 1]
[0128] [Production of resin particle dispersion] Production Example X1 (Production of Resin Particle Dispersion X-1) 1000 g of Resin A-1 and 1000 g of methyl ethyl ketone were placed in a 5 L vessel equipped with a stirrer, a reflux condenser, a dropping funnel, a thermometer, and a nitrogen inlet tube, and the resin was dissolved at 80° C. for 1 hour. A 5% by mass aqueous solution of sodium hydroxide was added to the resulting solution so that the degree of neutralization was 80 mol% relative to the acid value of the resin, and the mixture was stirred for 30 minutes. Next, while maintaining the temperature at 80°C, 2700g of deionized water was added over 60 minutes while stirring at 280r / min (circumferential speed 88m / min) to cause phase inversion emulsification. While continuing to maintain the temperature at 80°C, methyl ethyl ketone was distilled off under reduced pressure to obtain an aqueous dispersion of resin. Thereafter, while continuing to stir at 280r / min (circumferential speed 88m / min), the aqueous dispersion was cooled to 30°C, and deionized water was added so that the solid concentration was 25 mass%, to obtain resin particle dispersion X-1. The volume median particle diameter D of the obtained resin particles was 50 and CV values are shown in Table 2.
[0129] Production Examples X31, X2 and X3 (Production of Resin Particle Dispersions X-31, X-2 and X-3) Resin particle dispersions X-31, X-2, and X-3 were obtained in the same manner as in Production Example X1, except that Resin A-1 was replaced with Resin A-31, A-2, or A-3. 50 and CV values are shown in Table 2.
[0130] Production Example X4 (Production of Resin Particle Dispersion X-4) 200g of resin A-4, 110g of ethyl acetate, and 40g of 15% by mass sodium dodecylbenzenesulfonate aqueous solution "Neopelex G-15" (Kao Corporation, anionic surfactant) were placed in a 3L container equipped with a stirrer, reflux condenser, dropping funnel, thermometer, and nitrogen inlet tube, and the resin was dissolved at 70°C for 2 hours. 560g of deionized water at 70°C was added to the obtained solution, and dispersion treatment was performed for 30 minutes at an output of 350W using an ultrasonic homogenizer "UP-400S" (Hielscher). Thereafter, while maintaining the temperature at 70°C, ethyl acetate was distilled off under reduced pressure, deionized water was added, and the solid concentration was adjusted to 25% by mass, to obtain resin particle dispersion X-4. The volume median particle diameter D of the obtained resin particles was 50 and CV values are shown in Table 2.
[0131] Production Example P1 (Production of Resin Particle Dispersion P-1) 200g of resin A-1 and 200g of methyl ethyl ketone were placed in a 3L container equipped with a stirrer, reflux condenser, dropping funnel, thermometer and nitrogen inlet tube, and the resin was dissolved at 80°C for 1 hour. A 5% by mass aqueous solution of sodium hydroxide was added to the obtained solution so that the degree of neutralization was 75 mol% with respect to the acid value of resin A-1, and the solution was stirred for 30 minutes. Next, while maintaining the temperature at 80°C, 700g of deionized water was added over 50 minutes while stirring at 280 r / min (circumferential speed 88 m / min), and phase inversion emulsification was performed. While continuing to maintain the temperature at 80°C, methyl ethyl ketone was distilled off under reduced pressure to obtain an aqueous dispersion of the resin. Thereafter, the aqueous dispersion was cooled to 30°C while stirring at 280 r / min (circumferential speed 88 m / min), and deionized water was added so that the solid content concentration was 20% by mass, thereby obtaining a resin particle dispersion P-1. The volume median particle diameter D of the obtained resin particles 50and CV values are shown in Table 2.
[0132] [Table 2]
[0133] [Production of release agent particle dispersion] Production Example W1 (Production of Release Agent Particle Dispersion W-1) 25 g of deionized water, 120 g of resin particle dispersion P-1, and 60 g of paraffin wax "HNP-9" (manufactured by Nippon Seiro Co., Ltd., melting point 75°C) were added to a 1 L beaker, and the mixture was melted and stirred while maintaining the temperature at 90 to 95°C to obtain a molten mixture. The obtained molten mixture was dispersed for 20 minutes using an ultrasonic homogenizer "US-600T" (manufactured by Nippon Seiki Seisakusho Co., Ltd.) while maintaining the temperature at 90 to 95°C, and then cooled to room temperature (20°C). Deionized water was added to the obtained dispersion to adjust the solid concentration to 40 mass%, thereby obtaining a release agent particle dispersion W-1. The volume median particle diameter D of the release agent particles 50 The diameter was 0.29 μm and the CV value was 37%.
[0134] Production Example W2 (Production of Release Agent Particle Dispersion W-2) A release agent particle dispersion W-2 was obtained in the same manner as in Production Example W1, except that the type of release agent was changed to Fischer-Tropsch wax "FNP-0090" (manufactured by Nippon Seiro Co., Ltd., melting point 90°C). 50 The diameter was 0.26 μm and the CV value was 39%.
[0135] [Production of colorant particle dispersion] Production Example E1 (Production of Colorant Particle Dispersion E-1) In a beaker with an internal volume of 1 L, 100 g of CI Pigment Blue 15:3 (manufactured by Dainichiseika Color & Chemicals Co., Ltd., "ECB301", molecular weight 576), 167 g of 15 mass % sodium dodecylbenzenesulfonate aqueous solution "Neopelex G-15" (manufactured by Kao Corporation, anionic surfactant), and 102 g of deionized water were mixed, and dispersed at 20°C and a stirring blade rotation speed of 8000 r / min for 1 hour using a homogenizer "TKAGI HOMOMIXER 2M-03" (manufactured by Primix Corporation), and then processed 15 times at a pressure of 150 MPa using a homogenizer "Microfluidizer M-110EH" (manufactured by Microfluidics). Then, the mixture was passed through a 200 mesh filter, and deionized water was added so that the solid concentration was 20 mass %, to obtain a colorant particle dispersion E-1. The volume median particle diameter D of the colorant particles 50 The thickness was 0.12 μm and the CV value was 22%.
[0136] [Production of Water-soluble Addition Polymer F] Production Example F1 (Production of Water-Soluble Addition Polymer F-1) A raw material monomer mixture was prepared by mixing 31 parts by mass of acrylic acid (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.), 59 parts by mass of styrene (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.), and 10 parts by mass of α-methylstyrene (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.). Into a reaction vessel, 10 parts by mass of methyl ethyl ketone, 0.3 parts by mass of 2-mercaptopropionic acid (polymerization chain transfer agent), and 10% by mass of the raw material monomer mixture were placed and mixed, and the atmosphere was thoroughly replaced with nitrogen gas. Meanwhile, the remaining raw material monomer mixture, 0.27 parts by mass of the polymerization chain transfer agent, 40 parts by mass of MEK, and 1.1 parts by mass of an azo radical polymerization initiator (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., V-501; 4,4'-azobis(4-cyanovaleric acid)) were placed in a dropping funnel, and the monomer mixture in the reaction vessel was heated to 65°C while stirring under a nitrogen atmosphere, and the mixture in the dropping funnel was dropped over 3 hours. After 2 hours at 65°C from the end of the dropping, a solution in which 0.15 parts by mass of the polymerization initiator was dissolved in 2.5 parts by mass of MEK was added, and the mixture was further aged at 65°C for 2 hours and 70°C for 2 hours, followed by drying under reduced pressure to obtain a water-soluble addition polymer F-1 having a carboxy group. The acid value and weight average molecular weight of the obtained water-soluble addition polymer are shown in Table 3.
[0137] Production Example F2 (Production of Water-soluble Addition Polymer F-2) A water-soluble addition polymer F-2 having a carboxy group was obtained in the same manner as in Production Example F1, except that the raw material monomers, polymerization chain transfer agent, and polymerization initiator shown in Table 3 were used in the amounts (parts by mass) shown in Table 3. The polymerization chain transfer agent was placed in a reaction vessel at 0.41 parts by mass and in a dropping funnel at 0.37 parts by mass. The acid value and weight average molecular weight of the obtained water-soluble addition polymer are shown in Table 3.
[0138] Production Example F3 (Production of Water-soluble Addition Polymer F-3) A water-soluble addition polymer F-3 having a carboxy group was obtained in the same manner as in Production Example F1, except that the raw material monomers, polymerization chain transfer agent, and polymerization initiator shown in Table 3 were used in the amounts (parts by mass) shown in Table 3. The polymerization chain transfer agent was placed in a reaction vessel at 0.6 parts by mass and in a dropping funnel at 0.5 parts by mass. The acid value and weight average molecular weight of the obtained water-soluble addition polymer are shown in Table 3.
[0139] Production Example F4 (Production of Water-soluble Addition Polymer F-4) A water-soluble addition polymer F-4 having a carboxy group was obtained in the same manner as in Production Example F1, except that the raw material monomers, polymerization chain transfer agent, and polymerization initiator shown in Table 3 were used in the amounts (parts by mass) shown in Table 3. The polymerization chain transfer agent was placed in a reaction vessel at 3.0 parts by mass and in the dropping funnel at 2.7 parts by mass. The acid value and weight average molecular weight of the obtained water-soluble addition polymer are shown in Table 3.
[0140] Production Example F5 (Production of Water-soluble Addition Polymer F-5) Into a reaction vessel were mixed 53 parts by mass of methacrylic acid (reagent manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.), 47 parts by mass of benzyl methacrylate (reagent manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.), and 229 parts by mass of 99.5% ethanol, and the atmosphere was thoroughly replaced with nitrogen gas. Under a nitrogen atmosphere, the monomer mixture in the reaction vessel was heated to 60°C while being stirred, and a polymerization initiator solution prepared by dissolving 2.2 parts by mass of a polymerization initiator (V-65B; 2,2-azobis(2,4 dimethylvaleronitrile) in 2.5 parts by mass of 99.5% ethanol was added all at once, and the polymerization reaction was carried out for 4 hours. The solution after polymerization was reprecipitated using hexane and dried under reduced pressure to obtain a water-soluble addition polymer F-5 having a carboxy group. The acid value and weight average molecular weight of the obtained water-soluble addition polymer are shown in Table 3.
[0141] [Table 3]
[0142] [Production of fusion dispersion solution] Production Example G1 (Production of Fusion Dispersant Solution G-1) In a 2L vessel equipped with a stirrer, reflux condenser, thermometer and nitrogen inlet tube, 200g of water-soluble addition polymer F-1, 450g of deionized water, and 5% by mass aqueous sodium hydroxide solution were added so that the degree of neutralization was 100mol% relative to the acid value of the water-soluble addition polymer F-1, and the resin was dissolved in water at 80°C for 3 hours while stirring at 280r / min (circumferential speed 88m / min). After cooling to 30°C, deionized water was added so that the solid concentration was 17% by mass, to obtain a fusion dispersant solution G-1.
[0143] Production Example G2 (Production of Fusion Dispersant Solution G-2) A fusion dispersant solution G-2 (solid concentration 17% by mass) was obtained in the same manner as in Production Example G1, except that 200 g of water-soluble addition polymer F-2, 800 g of deionized water, and 5% by mass aqueous sodium hydroxide solution were placed in a 2 L container so that the degree of neutralization was 100 mol% relative to the acid value of the water-soluble addition polymer F-2.
[0144] Production Example G3 (Production of Fusion Dispersant Solution G-3) A fusion dispersant solution G-3 (solid concentration 17% by mass) was obtained in the same manner as in Production Example G1, except that 200 g of water-soluble addition polymer F-3, 500 g of deionized water, and 5% by mass sodium hydroxide aqueous solution were placed in a 2 L container so that the degree of neutralization with respect to the acid value of the water-soluble addition polymer F-3 was 100 mol%.
[0145] Production Example G4 (Production of Fusion Dispersant Solution G-4) A fusion dispersant solution G-4 (solid concentration 17% by mass) was obtained in the same manner as in Production Example G1, except that 200 g of water-soluble addition polymer F-4, 500 g of deionized water, and 5% by mass aqueous sodium hydroxide solution were placed in a 2 L container so that the degree of neutralization with respect to the acid value of the water-soluble addition polymer F-4 was 100 mol%.
[0146] Production Example G5 (Production of Fusion Dispersant Solution G-5) A fusion dispersant solution G-5 (solid concentration 17% by mass) was obtained in the same manner as in Production Example G1, except that 200 g of water-soluble addition polymer F-5, 250 g of deionized water, and 5% by mass aqueous sodium hydroxide solution were placed in a 2 L container so that the degree of neutralization was 100 mol% relative to the acid value of the water-soluble addition polymer F-5.
[0147] Production Example G6 (Production of Fusion Dispersant Solution G-6) 150 g of sodium polyoxyethylene lauryl ether sulfate "EMAL E-27C" (Kao Corporation, anionic surfactant, effective concentration 27% by mass) was dissolved in 88 g of deionized water to obtain a fusion dispersant solution G-6 (solid concentration 17% by mass).
[0148] Production Example G7 (Production of Fusion Dispersant Solution G-7) 40 g of β-naphthalenesulfonic acid formalin condensate sodium salt “Demol N” (manufactured by Kao Corporation) was dissolved in 195 g of deionized water to obtain a fusion dispersant solution G-7 (solid content concentration: 17% by mass).
[0149] Example 1 Into a 3 L four-neck flask equipped with a dehydration tube, a stirrer, and a thermocouple, 800 g of resin particle dispersion X-1, 52 g of release agent particle dispersion W-1, 52 g of release agent particle dispersion W-2, and 101 g of colorant particle dispersion E-1 were placed and mixed at a temperature of 25° C. While stirring the resulting mixture, a solution obtained by dissolving 51 g of ammonium sulfate in 900 g of deionized water and adding a 4.8 mass % potassium hydroxide aqueous solution to adjust the pH to 8.0 was added dropwise over 60 minutes at 25° C., and the temperature was then raised to 55° C. over one hour, and the volume median particle diameter D of the aggregated particles was measured. 50 The temperature was maintained at 55° C. until the particle size reached 6.0 μm, thereby obtaining a dispersion of aggregated particles 1. To the obtained dispersion liquid of aggregated particles 1, 43 g of fused dispersant solution G-1, 247 g of deionized water, and 170 g of 4.8 mass% potassium hydroxide aqueous solution were added to adjust the solid content concentration to 10 mass%. Then, the temperature was raised to 70°C over 1 hour, and the temperature was maintained at 70°C until the circularity reached 0.970, thereby obtaining a dispersion liquid of fused particles in which aggregated particles 1 were fused. The obtained dispersion of fused particles was cooled to 30°C and passed through a stainless steel (SUS) mesh with 45 μm openings to collect coarse particles of 45 μm or more. The dispersion after the coarse particle collection was suction filtered to separate the solid content, which was then washed with deionized water at 25°C and suction filtered at 25°C for 2 hours. The solids were then vacuum dried at 33°C for 24 hours using a vacuum constant temperature dryer "DRV622DA" (manufactured by ADVANTEC) to obtain toner particles. The physical properties of the toner particles are shown in Table 4. 100 parts by weight of toner particles, 2.5 parts by weight of hydrophobic silica "RY50" (manufactured by Nippon Aerosil Co., Ltd., number average particle size: 0.04 μm), and 1.0 part by weight of hydrophobic silica "Cabosil (registered trademark) TS720" (manufactured by Cabot Corporation, number average particle size: 0.012 μm) were placed in a Henschel mixer and stirred, and the mixture was passed through a 150 mesh sieve to obtain toner 1.
[0150] [Toner evaluation method] [Toner Coarse Particle Amount] The collected coarse particles were dried for one day by aeration in a Buchner funnel. The mass of the dried coarse particles was then measured. Next, using an infrared moisture meter "FD-230" (Kett Electric Laboratory Co., Ltd.), the moisture (mass%) of 5 g of the coarse particles was measured at a drying temperature of 150°C and measurement mode 96 (monitoring time 2.5 minutes, moisture content fluctuation range 0.05%), and the solid content concentration of the coarse particles was calculated according to the following formula. Solids concentration of coarse particles (mass%) = 100 - moisture (mass%) The mass of the coarse particles, the solid content concentration of the coarse particles, and the theoretical yield of the toner particles were applied to the following formula to obtain the amount of coarse particles (the content of coarse toner particles in the toner particles). Amount of coarse particles (mass%) = Mass of coarse particles (g) × Solid content concentration of coarse particles (mass%) / Theoretical yield of toner particles (g)
[0151] [Charge retention rate] -Calculation of charge amount under normal temperature and humidity- Toner 1 was stored for 7 days at a temperature of 25°C and a relative humidity of 50%. After storage, 2.1 g of Toner 1 and 27.9 g of silicone ferrite carrier (manufactured by Kanto Denka Kogyo Co., Ltd., average particle size: 40 μm) were placed in a 50 mL cylindrical polypropylene bottle (manufactured by Nikko Hansen Co., Ltd.) and mixed using a ball mill at 250 r / min. Thereafter, the charge amount was measured under the following conditions using a "q / m-meter" (manufactured by Epping Co., Ltd.). Mesh size: 635 mesh (opening: 24 μm, stainless steel) Soft blow: Blow pressure (1000V) ·Suction time: 90 seconds The charge amount is calculated by the following formula, and a larger absolute value indicates better chargeability. Charge amount (μC / g) = Total charge after 90 seconds (μC) / Amount of toner absorbed (g) -Calculation of charge amount under high temperature and high humidity conditions- The same measurements as above were carried out at a temperature of 40° C. and a relative humidity of 66%. -Calculation of charge retention rate- Calculated using the following formula. Charge retention rate (%) = 100 x charge amount under high temperature and high humidity (μC / g) / charge amount under normal temperature and normal humidity (μC / g)
[0152] Examples 2 to 5, Comparative Examples 1 and 2 (Production of Toners 2 to 5, c1 and c2) A toner was produced and evaluated in the same manner as in Example 1, except that the fusion dispersant solution used was changed as shown in Table 4. The physical property values of the obtained toner particles and the evaluation results of the toner are shown in Table 4.
[0153] Example 6 (Production of Toner 6) A toner was produced and evaluated in the same manner as in Example 1, except that a mixture of 20 g of fusion dispersant solution G-1 and 23 g of fusion dispersant solution G-4 was used instead of 43 g of fusion dispersant solution G-1. The physical properties of the obtained toner particles and the evaluation results of the toner are shown in Table 4.
[0154] Examples 7 to 10 (Production of Toners 7 to 10) A toner was produced and evaluated in the same manner as in Example 1, except that the resin particle dispersion liquid used was changed as shown in Table 4. The physical property values of the obtained toner particles and the evaluation results of the toner are shown in Table 4.
[0155] Example 11 (Production of Toner 11) Toner 11 was produced and evaluated in the same manner as in Example 1, except that the amount of the fusion dispersant solution used was changed as shown in Table 4 and the amount of deionized water added to the dispersion of aggregated particles 1 was changed to 282 g. The physical property values of the obtained toner particles and the evaluation results of the toner are shown in Table 4.
[0156] Example 12 (Production of Toner 12) Toner 12 was produced and evaluated in the same manner as in Example 1, except that the amount of the fusion dispersant solution used was changed as shown in Table 4 and the amount of deionized water added to the dispersion of aggregated particles 1 was changed to 275 g. The physical property values of the obtained toner particles and the evaluation results of the toner are shown in Table 4.
[0157] Example 13 (Production of Toner 13) Toner 13 was produced and evaluated in the same manner as in Example 1, except that the amount of the fusion dispersant solution used was changed as shown in Table 4, and the amount of deionized water added to the dispersion of aggregated particles 1 was changed to 145 g. The physical property values of the obtained toner particles and the evaluation results of the toner are shown in Table 4.
[0158] Example 14 (Production of Toner 14) Toner 14 was produced and evaluated in the same manner as in Example 1, except that the amount of the fusion dispersant solution used was changed as shown in Table 4 and the amount of deionized water added to the dispersion of aggregated particles 1 was changed to 0 g. The physical property values of the obtained toner particles and the evaluation results of the toner are shown in Table 4.
[0159] [Table 4]
[0160] The toner obtained by the manufacturing method of the present invention has a low content of coarse particles (Examples 1 to 14). In addition, the toner obtained by the manufacturing method of the present invention has a high charge amount retention rate, and therefore, it is found that the charge amount is excellent even after storage under high temperature and high humidity conditions (Examples 1 to 14). In contrast, when sodium polyoxyethylene lauryl ether sulfate was used in place of the water-soluble addition polymer of an aromatic group-containing monomer and a hydrophilic monomer in step 2 (Comparative Example 1), and when sodium salt of naphthalenesulfonic acid-formaldehyde condensate was used (Comparative Example 2), the amount of coarse particles in the toner was large and the charge amount retention rate was low.
Claims
1. A method for producing a toner for developing an electrostatic image, comprising the following steps 1 and 2 in this order: Step 1: A step of aggregating resin particles in an aqueous medium to obtain aggregated particles; Step 2: A step of adding 0.2 parts by mass or more and 30 parts by mass or less of a water-soluble addition polymer of an aromatic group-containing monomer and a hydrophilic monomer to the aggregated particles obtained in step 1 relative to 100 parts by mass of the binder resin in the aggregated particles, and then heating the mixture to fuse the mixture to obtain fused particles.
2. 2. The method for producing a toner for developing electrostatic images according to claim 1, wherein in step 2, an aqueous solution of a water-soluble addition polymer of an aromatic group-containing monomer and a hydrophilic monomer is added.
3. 3. The method for producing a toner for developing an electrostatic image according to claim 1, wherein the hydrophilic monomer has a carboxy group.
4. 4. The method for producing a toner for developing electrostatic images according to claim 3, wherein the water-soluble addition polymer of the aromatic group-containing monomer and the hydrophilic monomer has an acid value of 50 mgKOH / g or more and 500 mgKOH / g or less.
5. 3. The method for producing a toner for developing electrostatic images according to claim 1, wherein the amount of structural units derived from the hydrophilic monomer in the water-soluble addition polymer of the aromatic group-containing monomer and the hydrophilic monomer is from 5% by mass to 70% by mass.
Citation Information
Patent Citations
Method for manufacturing toner for electrostatic charge image development
JP2021182045A